Drop-resistant reinforced microcrystalline glass with safe stress state, preparation method and application thereof

By introducing sodium ions into spinel microcrystalline glass for chemical strengthening, lithium-free reinforced microcrystalline glass is formed, which solves the problems of insufficient drop resistance and safety hazards in the prior art, and takes into account both high-pressure stress and safe stress states.

CN118184148BActive Publication Date: 2025-03-25CHONGQING AUREAVIA HI TECH GLASS CO LTD

Patent Information

Application Number
CN202211735522.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-25
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

After chemical strengthening, existing spinel microcrystalline glasses are difficult to achieve high-pressure and safe stress states, resulting in insufficient anti-fall performance and safety hazards.

Method used

Chemical strengthening is carried out by introducing sodium ions into spinel microcrystalline glass, lithium-free reinforced microcrystalline glass with specific stress distribution characteristics is formed, ensuring that it maintains a safe stress state while obtaining excellent drop resistance.

Benefits of technology

It has achieved that reinforced microcrystalline glass does not form a large number of small fragments after falling impact, avoids safety hazards, and has excellent anti-fall and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118184148B_ABST
    Figure CN118184148B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of microcrystalline glass, and specifically to a drop-resistant strengthened microcrystalline glass with a safe stress state, a preparation method and an application thereof, wherein the strengthened microcrystalline glass comprises a compressive stress layer and a tensile stress layer, and a spinel crystal main phase; the strengthened microcrystalline glass substantially does not contain Li2O in its composition, and the strengthened microcrystalline glass satisfies the following conditions: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t; exp((|CT_CV||CT_AV|) / (t / 2-DOL_0)*2)<1.30; wherein t is the thickness of the microcrystalline glass. The strengthened microcrystalline glass of the present invention has specific stress characteristics, has excellent drop resistance and safety performance, can achieve an optimal safe stress state, will not undergo explosive cracking due to a slight impact, will not self-explode, and will not produce a large number of small fragments even after being broken by impact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microcrystalline glass, and in particular to a drop-resistant and strengthened microcrystalline glass with a safe stress state, a preparation method and an application thereof. Background Art

[0002] At present, glass-ceramics (glass ceramics) materials have become a better choice for screen covers due to their excellent mechanical properties and light transmittance. Among the many glass-ceramics, spinel glass-ceramics with spinel as the main crystal phase has gradually attracted the attention of people in the industry because of its high Young's modulus and shear modulus.

[0003] In order to achieve chemical strengthening and toughening of spinel glass-ceramics, alkali metal ions need to be introduced into the glass to complete ion exchange. Considering that the introduction of lithium has many disadvantages, such as high cost, low stress generated by exchange under the same exchange amount, and easy precipitation of impurities when added in large amounts, resulting in reduced transparency of spinel glass-ceramics, etc. The inventors thought of introducing only sodium ions into the glass to achieve chemical strengthening and toughening.

[0004] Chemical strengthening is the use of ion exchange process, that is, the use of alkali metal ions with large ion radius in the salt bath to replace the alkali metal ions with small ion radius in the glass, resulting in a volume difference of the exchanged ions, thereby generating a high to low compressive stress on a certain surface layer of the glass, thereby hindering and delaying the expansion of glass microcracks, so as to achieve the purpose of improving the mechanical strength of the glass. The strengthened microcrystalline glass treated by the ion exchange process generates compressive stress on the surface and corresponding tensile stress inside. Chemically strengthened microcrystalline glass is a stress balance body. If the compressive stress is low, the strength of the obtained strengthened microcrystalline glass is not high enough to meet the customer's requirements for high drop resistance of the product; if the compressive stress is too high, although a very high-strength strengthened microcrystalline glass can be obtained, it will also cause a very high tensile stress to form inside the strengthened microcrystalline glass. Such strengthened microcrystalline glass will have safety hazards. It is easy to cause explosive cracking under a slight impact, and even self-explosion, which seriously affects the reliability of the product and even has a serious impact on the personal safety of customers. Summary of the invention

[0005] The technical problem to be solved by the present invention is how to ensure that the strengthened microcrystalline glass with spinel as the main crystal phase has both high pressure stress to meet the requirements of high drop resistance and excellent safety performance to maintain a safe stress state.

[0006] The inventors have devoted themselves to research and found that the drop resistance and safety performance of strengthened microcrystalline glass are related to the stress distribution characteristics, and the lithium-free spinel strengthened microcrystalline glass with specific stress distribution characteristics can maintain a safe stress state while achieving excellent drop resistance, and has excellent safety performance. If only the excellent drop resistance is considered without considering the safety performance, a large number of small fragments may be formed after the glass is broken, and it will be difficult to continue to use it as a display screen, and the small fragments are easy to fly everywhere, causing safety hazards. Strengthened microcrystalline glass with both excellent drop impact resistance and excellent safety performance will not form a large number of small fragments that are easy to fly everywhere even after being broken by a drop impact. Not only can it avoid safety hazards, but the glass used as a display screen can also be used in an emergency after falling and breaking.

[0007] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a high-stress lithium-free transparent spinel strengthened glass-ceramics with a safe stress state, and to intuitively characterize the safe stress state of the strengthened glass-ceramics in a non-destructive manner.

[0008] Specifically, the present invention provides the following technical solutions:

[0009] In one aspect, the present invention provides a drop-resistant tempered glass-ceramic with a safe stress state, wherein the tempered glass-ceramic comprises a compressive stress layer and a tensile stress layer, wherein the tempered glass-ceramic comprises spinel crystals, and the spinel crystals are the main crystalline phase of the tempered glass-ceramic; the tempered glass-ceramic substantially does not contain Li2O, and the Li2O content is less than 0.01% in mol%;

[0010] The strengthened glass-ceramics meets the following conditions:

[0011] CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t;

[0012] exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2)<1.30;

[0013] Where t is the thickness of the glass-ceramic in μm, DOL_0 is in μm, and CS_50, |CT_CV|, and |CT_AV| are in MPa.

[0014] Preferably, a drop and breakage test is performed on the above-mentioned strengthened microcrystalline glass. Among the fragment particles generated when the above-mentioned strengthened microcrystalline glass falls and breaks, the fragment particles whose longest side of the vertical projection on the two-dimensional drawing is greater than 5 mm account for more than 70% of the total weight of the glass, preferably more than 80%.

[0015] Preferably, the tempered glass-ceramics satisfies 500MPa≥CS_50≥140MPa; and / or 200MPa≥|CT_AV|≥70MPa; and / or 0.22t≥DOL_0≥0.15t.

[0016] Preferably, the tempered glass-ceramics has |CT_CV|≥80 MPa, preferably 300 MPa≥|CT_CV|≥80 MPa, and the unit of |CT_CV| is MPa.

[0017] Preferably, the surface K2O concentration of the strengthened glass-ceramics is ≥ 9.00 wt%, preferably 9.00-16.00 wt%.

[0018] Preferably, the CT_LD of the strengthened glass-ceramics is 40000 MPa / mm-85000 MPa / mm, preferably 45000 MPa / mm-85000 MPa / mm, and more preferably 48000 MPa / mm-85000 MPa / mm.

[0019] Preferably, the crystallinity of the strengthened microcrystalline glass is ≥20.00wt%; preferably, the crystallinity is 20.00-50.00wt%; further preferably, the crystallinity is 30.00-50.00wt%; more preferably, the crystallinity is 35.00-45.00wt%.

[0020] Preferably, in the strengthened glass-ceramics, the average grain size is ≤15.0 nm, preferably 1.0 to 15.0 nm, more preferably 1 to 10 nm, and more preferably 4.5 to 8.0 nm;

[0021] And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened microcrystalline glass also includes a secondary crystalline phase of tetragonal zirconia.

[0022] Preferably, the composition of the strengthened microcrystalline glass tensile stress layer includes, in terms of mol% of oxides: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%.

[0023] Preferably, in the tensile stress layer of the strengthened glass-ceramics:

[0024] The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed as a molar percentage of oxides:

[0025] The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.18, and the preferred value of A is 0.05 to 0.15.

[0026] (1)A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3;

[0027] and / or,

[0028] The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.80, and the preferred value of B is 0.60 to 0.78.

[0029] (2)B=3.8×Na2O+B2O3+4.5×MgO+6.0×ZnO-0.4×Al2O3-SiO2.

[0030] Preferably, in the tensile stress layer of the strengthened glass-ceramics, the molar percentage of SiO2 is 38.00-44.00%; and / or, the molar percentage of Na2O is 7.20-13.00%, preferably 7.20-12.00%.

[0031] And / or, the molar percentage of Al2O3 is 25.50-28.00%;

[0032] And / or, the molar percentage of MgO is 5.00-7.00%, preferably 5.00-6.50%;

[0033] And / or, the molar percentage of ZnO is 8.00-12.00%, preferably 8.00-10.50%;

[0034] And / or, the molar percentage of B2O3 is 3.00-7.00%, preferably 3.00-6.50%.

[0035] Preferably, in the tensile stress layer of the strengthened glass-ceramics, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

[0036] Preferably, in the tensile stress layer of the strengthened glass-ceramics:

[0037] The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides:

[0038] The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%, preferably 34.00 to 46.00%.

[0039] (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3);

[0040] and / or,

[0041] The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%, preferably 60.00 to 75.00%.

[0042] (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

[0043] Preferably, the tensile stress layer of the strengthened glass-ceramics contains: no BaO, with the content of BaO being less than 0.01% by mol%; and / or no TiO2, with the content of TiO2 being less than 0.01% by mol%.

[0044] Preferably, the strengthened glass-ceramics is transparent in the visible light range.

[0045] Preferably, the Vickers hardness of the strengthened glass-ceramics is 700-900 kgf / mm 2 .

[0046] Preferably, the fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 ; preferably greater than or equal to 1.20MPa·m 1 / 2 , more preferably greater than or equal to 1.50 MPa·m 1 / 2 .

[0047] Preferably, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-mesh sandpaper, and the average sandpaper drop resistance height of the tempered glass-ceramics is greater than 1.5 m, preferably greater than or equal to 1.80 m, further preferably 1.80 to 2.50 m, and more preferably 2.00 to 2.50 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

[0048] Preferably, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper. If the glass sample does not break after falling, it is marked as passed. The pass rate of the tempered glass-ceramics is ≥50%, preferably ≥60%, and more preferably ≥70%. The pass rate is based on the testing of at least 10 samples.

[0049] Preferably, the Young's modulus of the strengthened glass-ceramics is ≥ 100 GPa, preferably Young's modulus ≥

[0050] 110 GPa, more preferably 114 GPa ≤ Young's modulus ≤ 140 GPa.

[0051] Preferably, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test under the conditions of 85°C and 85% relative humidity, and its high temperature and high humidity failure time is ≥240h, preferably ≥300h, and more preferably ≥360h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

[0052] On the other hand, the present invention also provides a method for preparing the above-mentioned strengthened glass-ceramics, comprising the following steps: (I) preparation of chemically strengthened glass-ceramics: the chemically strengthened glass-ceramics are prepared from substrate glass by heat treatment; (II) preparation of strengthened glass-ceramics: the chemically strengthened glass-ceramics obtained in step (I) are subjected to chemical strengthening treatment to obtain the strengthened glass-ceramics as claimed in any one of claims 1 to 21; the strengthened glass-ceramics contain spinel crystals, and the spinel crystals are the main crystalline phase of the strengthened glass-ceramics; the composition of the strengthened glass-ceramics does not substantially contain Li2O, and the Li2O is less than 0.01% in mol%;

[0053] The strengthened glass-ceramics meets the following conditions:

[0054] CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t;

[0055] exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2)<1.30;

[0056] Wherein, t is the thickness of the glass-ceramic, in μm.

[0057] Preferably, in the above preparation method, the chemical strengthening treatment includes a single-step strengthening method or a multi-step strengthening method; preferably, the salt bath for the chemical strengthening treatment is a molten salt containing a potassium salt.

[0058] Preferably, in the above preparation method, the concentration of potassium salt in the chemical strengthening salt bath is 60wt% to 100wt%; the temperature of the chemical strengthening salt bath is 380°C to 600°C, preferably 400°C to 550°C.

[0059] On the other hand, the present invention also provides a chemically strengthened glass-ceramic for preparing the above-mentioned strengthened glass-ceramic, wherein the chemically strengthened glass-ceramic contains spinel crystals, and the spinel crystals are the main crystalline phase of the glass-ceramic; preferably, the composition of the chemically strengthened glass-ceramic contains the following proportions of oxides in mol%: SiO238.00~48.00%, Al2O325.50~30.00%, ZrO23.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na2O 7.20~14.00%, B2O33.00~8.00%, K2O 0~2.00% and Y2O30~1.00%; wherein the chemically strengthened glass-ceramic does not basically contain Li2O, and in mol%, Li2O is less than 0.01%.

[0060] Preferably, in the chemically strengthened glass-ceramics, the composition of the chemically strengthened glass-ceramics, expressed in terms of the content expressed in molar percentage of oxides, satisfies:

[0061] A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3, wherein A≤0.18, and the preferred value of A is 0.05-0.15;

[0062] and / or, B = 3.8 × Na2O + B2O3 + 4.5 × MgO + 6.0 × ZnO - 0.4 × Al2O3 - SiO2, wherein B ≤ 0.80, preferably the value of B is 0.60 to 0.78;

[0063] and / or, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3), wherein X=30.00-50.00%, preferably X=34.00-46.00%;

[0064] and / or, Y = (2.7 × Na2O + 1.8 × (Al2O3-MgO-ZnO)) / (SiO2 + Al2O3-MgO-ZnO + Na2O + K2O + B2O3), wherein Y = 60.00-80.00%, preferably Y = 60.00-75.00%;

[0065] And / or, in the chemically strengthened glass-ceramics, the molar percentages of the components Al2O3, MgO, and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

[0066] Preferably, in the above-mentioned chemically strengthened glass-ceramics, the spinel crystal is (Zn, Mg)Al2O4; and / or, the chemically strengthened glass-ceramics also include secondary crystalline tetragonal zirconia; and / or, the chemically strengthened glass-ceramics has a crystallinity ≥20.00wt%; preferably, the crystallinity is 20.00~50.00wt%; further preferably, the crystallinity is 30.00~50.00wt%; more preferably, the crystallinity is 35.00~45.00wt%; and / or, in the chemically strengthened glass-ceramics, the average grain size is ≤15.0nm, preferably 1.0~15.0nm, further preferably 1.0~10.0nm, more preferably 4.5~8.0nm; and / or, the Young's modulus of the chemically strengthened glass-ceramics is ≥100GPa, preferably Young's modulus ≥110GPa, more preferably 114GPa<Young's modulus≤140GPa.

[0067] On the other hand, the present invention also provides the use of the above-mentioned strengthened microcrystalline glass or the strengthened microcrystalline glass prepared by the above-mentioned preparation method or the above-mentioned chemically strengthened microcrystalline glass in mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

[0068] Beneficial effects of the present invention:

[0069] The drop-resistant tempered micro-ceramic with a safe stress state of the present invention has specific stress characteristics, has both excellent drop resistance and excellent safety performance, can achieve the best safe stress state, will not cause explosive cracking due to slight impact, will not produce self-explosion, and will not produce a large number of small fragments even after impact and breakage. The present invention provides a non-destructive solution that can quickly and accurately determine whether the lithium-free tempered micro-ceramic with spinel as the main crystal phase is in a safe stress state. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 is a thermogravimetric analysis curve of the substrate glass of Example 1;

[0071] Figure 2 is the XRD diffraction pattern of the chemically strengthened glass-ceramics of Example 1;

[0072] Figure 3 1 is the transmittance curve of the chemically strengthened glass-ceramics of Example 1 under different wavelength conditions;

[0073] Figure 4 This is a diagram of the melting results of the substrate glass of Example 1;

[0074] Figure 5This is a diagram showing the melting results of the substrate glass of Example 3;

[0075] Figure 6 This is an appearance diagram of the chemically strengthened glass-ceramics of Example 3;

[0076] Figure 7 This is a diagram of the melting results of the substrate glass of Comparative Example 1;

[0077] Figure 8 This is a diagram showing the melting results of the substrate glass of Comparative Example 2;

[0078] Fig. 9 This is a diagram of the melting results of the substrate glass of Comparative Example 3;

[0079] Fig.10 This is a diagram of the melting results of the substrate glass of Comparative Example 6;

[0080] Fig.11 This is an appearance diagram of the chemically strengthened glass-ceramics of Comparative Example 18;

[0081] Fig.12 The diagram is a diagram showing the drop and breakage results of the strengthened glass-ceramics of Examples 1-6;

[0082] Fig.13 The diagram is a diagram showing the drop and breakage results of the strengthened glass-ceramics of Examples 7-12;

[0083] Fig.14 This is a diagram showing the drop and breakage results of the strengthened glass-ceramics of Example 13;

[0084] Fig.15 The graph is a drop and breakage result diagram of the strengthened glass-ceramics of Comparative Examples 19-24;

[0085] Fig.16 This is a distribution diagram of the maximum size of fragments of the strengthened microcrystalline glass after falling and breaking into pieces in Example 2 and Comparative Example 20. DETAILED DESCRIPTION

[0086] In the present invention, unless otherwise specified in specific circumstances, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoint values, as well as all integers and fractions within the range, and are not limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A; and / or B" means only A, or only B, or both A and B.

[0087] As used herein, the language "substantially free of" or "free of" when used to describe constituent components of a composition, batch, melt or article refers to constituent components that have not been actively added or dosed into the composition, batch, melt or article but may be present in small amounts of less than about 0.01% (on an oxide mole basis) as a contaminant and / or due to the inherent degree of uncertainty attributable to any measurement or analytical technique.

[0088] In the present invention, the chemically strengthened glass-ceramics is a type of solid composite material that is prepared by targeted controlled heat treatment of the substrate glass and contains both a glass phase and a crystal phase (microcrystalline phase, crystalline phase, crystalline phase). It should be understood that both the crystal phase and the crystal grain refer to the crystals precipitated in the glass-ceramics, but the description methods are different. The crystal phase is the microscopic structure of the crystal, which is determined by the conformation and arrangement of the polymer chains in the crystal.

[0089] In the present invention, strengthened glass-ceramics refers to a solid composite material obtained by chemically strengthening glass-ceramics, also known as chemically strengthened glass-ceramics.

[0090] It should be understood that during high-temperature chemical strengthening treatment, the alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the salt bath / molten salt will replace the alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the microcrystalline glass, thereby generating an exchange ion volume difference and generating compressive stress on the surface of the microcrystalline glass.

[0091] In the present invention, the base glass refers to glass that has not been subjected to nucleation treatment, crystallization treatment, and strengthening treatment.

[0092] In the present invention, nucleation treatment refers to growing small crystal nuclei from nucleating substances in the glass through heat treatment; crystallization treatment refers to growing certain crystals based on the crystal nuclei through heat treatment.

[0093] In the present invention, the nucleation temperature refers to the temperature at which crystal nuclei are formed.

[0094] In the present invention, the crystallization temperature refers to the temperature at which the target crystal growth rate can be controlled.

[0095] In the present invention, the optical b value represents the yellow-blue value of the material. The optical b value in the present invention is the b value of transmitted light. A positive optical b value indicates that the material is blue.

[0096] Transmittance refers to the ratio of the radiation energy projected and transmitted through the object to the total radiation energy projected on the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side. It should be understood that when a certain wavelength is irradiated on the glass surface, light will be reflected, absorbed and transmitted, and the ratio of the intensity of the transmitted part to the intensity of the incident light is the transmittance.

[0097] In the present invention, the transmittance result of the microcrystalline glass at a wavelength of 550nm refers to the average transmittance of multiple glass samples of the same batch measured at a wavelength of 550nm, and at least 5 samples of each batch of microcrystalline glass are taken for testing. In the present invention, a Konica Minolta spectrophotometer CM-3600A is used to test the transmittance of each glass sample at a wavelength of 550nm.

[0098] In the present invention, fogging refers to a semi-transparent state due to larger crystals or phase separation in the microcrystalline glass / glass ceramics, which is a state between transparency and devitrification.

[0099] In the present invention, devitrification means that due to the large crystals or phase separation in the microcrystalline glass / glass ceramic, the transparent property of the glass is completely lost, and any image on the back cannot be seen through the glass.

[0100] In the present invention, SOC refers to the photoelastic coefficient. Photoelasticity mainly refers to the phenomenon of birefringence caused by anisotropy of transparent materials after being subjected to force. The value of the residual stress (MPa) inside the material can be obtained by measuring the photoelastic coefficient and birefringence.

[0101] In the present invention, the surface K2O concentration is equal to the K2O mass / total oxide mass, wherein the total oxide mass includes oxides such as SiO2, Al2O3, P2O5, ZrO2, Na2O, K2O, etc. that can be accurately tested by XRF, and does not include the content of oxides such as Li2O and B2O3 that cannot be accurately tested by XRF. The XRF test uses a non-standard test, and the concentration of elements or their oxides with atomic numbers 6 and below in the glass is not tested. That is, when calculating the K2O concentration obtained by the XRF test in the present invention, the total oxide mass does not include the mass of elements or their oxides with atomic numbers 6 and below in the glass.

[0102] In the present invention, Vickers hardness refers to a standard for expressing the hardness of a material proposed by Robert L. Smith and George E. Sandland of the United Kingdom at Vickers Ltd in 1921.

[0103] In the present invention, fracture toughness refers to the impedance value displayed by the material when there is a crack or a crack-like defect in the sample or component and the material no longer breaks rapidly with the increase of load, that is, when the so-called unstable fracture occurs.

[0104] In the present invention, CS_50 refers to the compressive stress value at a depth of 50 μm from the glass surface.

[0105] In the present invention, |CT_CV| refers to the absolute value of the maximum value of tensile stress, specifically refers to the absolute value of the maximum value of all tensile stresses in the tensile stress layer.

[0106] In the present invention, |CT_AV| refers to the absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.

[0107] In the present invention, DOL_0 refers to the depth of the compressive stress layer, also known as the depth of the compressive stress layer, which refers to the distance from any surface of the glass to a position close to the surface where the compressive stress is zero.

[0108] In a first aspect, in order to make the tempered microcrystalline glass have excellent anti-drop performance while maintaining a safe stress state and having excellent safety performance, the present invention provides a tempered microcrystalline glass with the following crystallization characteristics and stress characteristics.

[0109] In a specific embodiment of the present invention, a drop-resistant tempered glass-ceramic with a safe stress state, the tempered glass-ceramic comprises a compressive stress layer and a tensile stress layer, the tempered glass-ceramic comprises spinel crystals, and the spinel crystals are the main crystalline phase of the tempered glass-ceramic; the tempered glass-ceramic substantially does not contain Li2O;

[0110] The strengthened glass-ceramics meets the following conditions:

[0111] CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t;

[0112] exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2)<1.30;

[0113] Wherein, t is the thickness of the glass-ceramic in μm, DOL_0 in μm, and |CT_CV| and |CT_AV| in MPa. It should be understood that in the relationship exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2), the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained, and the unit does not participate in the calculation.

[0114] In some specific embodiments of the present invention, the thickness t of the strengthened glass-ceramics is 0.2-5.0 mm, preferably 0.3-2.0 mm, and more preferably 0.4-1.5 mm.

[0115] The general drop impact is a piercing type of damage. Sharp particles can easily break through the glass surface CS under impact, causing a pit with a depth of 30-50 microns. Then, cracks are formed at the pit and extend, breaking through the compressive stress area, thus breaking the glass. CS_50 represents the magnitude of the compressive stress at a depth of 50 microns. The greater the stress at this point, the more conducive it is to inhibit the formation of cracks at the pit. The deeper the DOL-O, the larger the area that hinders crack extension. CT-CV is the highest point of tensile stress, which is similar to the average value of tensile stress of CT-AV. It indirectly represents the magnitude of deep compressive stress. The better the stress performance, the more difficult it is for cracks to extend.

[0116] The inventors of the present invention have conducted in-depth research on the stress distribution characteristics of strengthened glass-ceramics with spinel as the main crystal phase, so that a specific spinel system glass-ceramics with high intrinsic strength can meet specific stress characteristics after strengthening, and finally obtain a strengthened glass-ceramics with excellent mechanical properties, especially excellent drop impact resistance, and excellent safety performance. The inventors found that high CS_50, |CT_CV| and |CT_AV| values ​​and high compressive stress layer depth DOL_0 give the strengthened glass-ceramics excellent deep stress characteristics, giving the lithium-free strengthened glass-ceramics with spinel as the main crystal phase excellent mechanical properties, especially excellent drop impact resistance. Combined with meeting the specific stress distribution, that is, meeting the specific relationship between |CT_CV|, |CT_AV, glass thickness and compressive stress layer depth, even if the strengthened glass-ceramics is broken, the fragments will not be too small, so that the strengthened glass-ceramics can maintain a safe stress state while meeting the excellent drop impact resistance, can avoid self-explosion and fragment splashing, and has excellent safety performance.

[0117] In some preferred embodiments of the present invention, CS_50 is 140MPa~500MPa; and / or, |CT_AV| is 70~200MPa; and / or, DOL_0 is 0.15t~0.22t, t is the thickness of the microcrystalline glass, which can improve the tolerance of the reinforced microcrystalline glass to damage and destruction caused by collision with sharp-angle objects such as sand, that is, it has excellent anti-drop performance.

[0118] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: |CT_CV|≥80MPa, preferably 80-300MPa.

[0119] In the present invention, CT_LD refers to tensile stress linear density, which is the ratio of the absolute value of the sum of tensile stresses of the strengthened microcrystalline glass measured by the SLP-2000 stress meter to the glass thickness. The microcrystalline glass is placed in a salt bath for ion exchange to form a compressive stress layer (i.e., a strengthening layer). During the ion exchange process, a tensile stress layer is formed inside the glass. The tensile stress layer has an upper boundary at a certain distance from the upper surface of the strengthened microcrystalline glass and a lower boundary at a certain distance from the lower surface of the strengthened glass. The tensile stress at a certain point on the line segment in the tensile stress layer, which is perpendicular to the upper boundary and the lower boundary and whose upper and lower endpoints fall on the upper boundary and the lower boundary respectively, is recorded as the tensile stress curve. The ratio of the definite integral of the tensile stress curve to the thickness of the strengthened microcrystalline glass is recorded as the tensile stress linear density. The tensile stress linear density of the strengthened microcrystalline glass of the present invention can reach 40000MPa / mm-85000MPa / mm.

[0120] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: the depth of the compressive stress layer DOL_0 ≥ 0.13t, preferably 0.22t ≥ DOL_0 ≥ 0.15t, where t is the thickness of the glass-ceramics. In some embodiments, DOL_0 may be 0.15t to 0.21t, 0.15t to 0.20t, 0.15t to 0.19t, 0.15t to 0.18t, 0.15t to 0.17t, 0.16t to 0.21t, 0.17t to 0.21t, 0.18t to 0.21t or 0.19t to 0.21t. In some embodiments, the DOL_0 of the strengthened glass-ceramics may be 0.13t, 0.15t, 0.16t, 0.17t, 0.18t, 0.19t, 0.20t, 0.21t or 0.22t, or within the numerical range DOL_0 formed by any two of the above specific values ​​as endpoints. Exemplarily, when the thickness of the strengthened glass-ceramics is 0.7 mm, the depth of the compressive stress layer DOL_0 is ≥ 91.00 μm, preferably 105-150 μm, and the depth of the compressive stress layer DOL_0 may be 91.00 μm, 105.00 μm, 112.00 μm, 119 μm, 126.00 μm, 133.00 μm, 140.00 μm, 147.00 μm or 154.00 μm, or within the numerical range DOL_0 formed by any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0121] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: |CT_CV|≥80MPa, preferably 300MPa≥|CT_CV|≥80MPa. In some embodiments, |CT_CV| may be 80-280MPa, 80-260MPa, 80-240MPa, 80-220MPa, 80-200MPa, 80-180MPa, 80-160MPa, 100-280MPa, 120-280MPa, 140-280MPa, 160-280MPa or 180-280MPa. In some embodiments, the |CT_CV| of the strengthened glass-ceramics may be 80 MPa, 100 MPa, 120 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa or 300 MPa, or be within a numerical range of |CT_CV| consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass having the desired performance of the present invention can be obtained.

[0122] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: |CT_AV|≥70MPa, preferably 200MPa≥|CT_AV|≥70MPa. In some embodiments, |CT_AV| may be 70-180MPa, 70-160MPa, 70-140MPa, 70-120MPa, 70-100MPa, 90-180MPa, 110-180MPa, 130-180MPa or 150-180MPa. In some embodiments, the |CT_AV| of the strengthened glass-ceramics may be 70MPa, 90MPa, 110MPa, 120MPa, 140MPa, 160MPa, 180MPa or 200MPa, or a |CT_AV| in a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0123] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: CS_50≥100MPa, preferably 500MPa≥CS_50≥140MPa. In some embodiments, CS_50 may be 140-480MPa, 140-460MPa, 140-440MPa, 140-420MPa, 140-400MPa, 140-380MPa, 140-360MPa, 140-340MPa, 160-480MPa, 180-480MPa, 200-480MPa, 220-480MPa, 240-480MPa, 260-480MPa or 280-480MPa. In some embodiments, the CS_50 of the strengthened glass-ceramics may be 100 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, 320 MPa, 340 MPa, 360 MPa, 380 MPa, 400 MPa, 420 MPa, 440 MPa, 460 MPa, 480 MPa or 500 MPa, or a CS_50 within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges as long as the glass having the desired properties of the present invention can be obtained.

[0124] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: CT_LD is 40000MPa / mm-85000MPa / mm, preferably 45000MPa / mm-85000MPa / mm, and more preferably 48000MPa / mm-85000MPa / mm. In some embodiments, CT_LD may be 40000-80000 MPa / mm, 40000-75000 MPa / mm, 40000-70000 MPa / mm, 40000-65000 MPa / mm, 40000-60000 MPa / mm, 45000-85000 MPa / mm, 50000 MPa / mm-85000 MPa / mm, 55000 MPa / mm-85000 MPa / mm, 60000 MPa / mm-85000 MPa / mm or 65000 MPa / mm-85000 MPa / mm. In some embodiments, the tensile stress linear density CT_LD of the strengthened glass-ceramics may be 40000MPa / mm, 45000MPa / mm, 50000MPa / mm, 55000MPa / mm, 60000MPa / mm, 65000MPa / mm, 70000MPa / mm, 75000MPa / mm, 80000MPa / mm or 85000MPa / mm, or a tensile stress linear density CT_LD within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass having the desired performance of the present invention can be obtained.

[0125] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2)<1.30; wherein t is the thickness of the glass-ceramics in μm, DOL_0 in μm, and |CT_CV| and |CT_AV| in MPa. In some embodiments, the value of exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2) may be 1.00-1.29, 1.00-1.28, 1.00-1.27, 1.00-1.26, 1.00-1.25, 1.01-1.29, 1.02-1.29, 1.03-1.29, 1.04-1.29, 1.05-1.29, or 1.05-1.25. In some embodiments, the value of exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2) may be 1.01, 1.02, 1.03, 1.04, 1.05, 1.25, 1.26, 1.27, 1.28 or 1.29, or a value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass having the desired properties of the present invention can be obtained.

[0126] In some preferred embodiments of the present invention, the surface K2O concentration of the strengthened glass-ceramics is ≥9.00wt%, preferably 9.00-16.00wt%. In some embodiments, the surface K2O concentration of the strengthened glass-ceramics may be 9.00-15.00wt%, 9.00-14.00wt%, 9.00-13.00wt%, 9.00-12.00wt%, 9.00-11.00wt%, 10.00-16.00wt%, 11.00-16.00wt%, 12.00-16.00wt%, 13.00-16.00wt% or 14.00-16.00wt%. In some embodiments, the surface K2O concentration of the strengthened glass-ceramics may be 9.00wt%, 10.00wt%, 11.00wt%, 12.00wt%, 13.00wt%, 14.00wt%, 15.00wt% or 16.00wt%, or a surface K2O concentration within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass having the desired properties of the present invention can be obtained.

[0127] In some preferred embodiments of the present invention, in the strengthened glass-ceramics, the spinel crystal is a zinc-magnesium spinel solid solution (Zn, Mg)Al2O4. In some preferred embodiments of the present invention, the strengthened glass-ceramics also includes a secondary crystalline tetragonal zirconia.

[0128] In some preferred embodiments of the present invention, the strengthened glass-ceramics is transparent in the visible light range.

[0129] In some preferred embodiments of the present invention, the Vickers hardness of the strengthened glass-ceramics is 700-900 kgf / mm 2 In some embodiments, the Vickers hardness may be 700 to 890 kgf / mm 2 ,700~880kgf / mm 2 、700~870kgf / mm 2 ,700~860kgf / mm 2 ,700~850kgf / mm 2 、700~840kgf / mm 2 、700~830kgf / mm 2 、700~820kgf / mm 2 、700~810kgf / mm 2 ,700~800kgf / mm 2 ,710~900kgf / mm 2 ,720~900kgf / mm 2 ,730~900kgf / mm 2 ,740~900kgf / mm 2 ,750~900kgf / mm 2 ,760~900kgf / mm 2 ,770~900kgf / mm 2 ,780~900kgf / mm 2 ,790~900kgf / mm 2 or 800~900kgf / mm 2 In some embodiments, the Vickers hardness of the strengthened glass-ceramics may be 700 kgf / mm 2 、710kgf / mm 2 、720kgf / mm 2 、730kgf / mm 2 、740kgf / mm 2 、750kgf / mm 2 , 760kgf / mm2, 770kgf / mm 2 、780kgf / mm2 、790kgf / mm 2 、800kgf / mm 2 、810kgf / mm 2 、820kgf / mm2、830kgf / mm 2 、840kgf / mm 2 、850kgf / mm 2 、860kgf / mm 2 、8700kgf / mm 2 、880kgf / mm 2 、890kgf / mm 2 or 900kgf / mm 2 , or a Vickers hardness within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0130] In some preferred embodiments of the present invention, the fracture toughness of the strengthened glass-ceramics is greater than or equal to 1.00 MPa·m 1 / 2 , preferably greater than or equal to 1.20 MPa·m 1 / 2 , more preferably greater than or equal to 1.50 MPa·m 1 / 2 In some embodiments, the fracture toughness may be 1.00 to 2.00 MPa·m 1 / 2 , 1.20~2.00MPa·m 1 / 2 1.40~2.00MPa·m 1 / 2 , 1.50~2.00MPa·m 1 / 2 1.00~1.80MPa·m 1 / 2 1.20~1.80MPa·m 1 / 2 1.40~1.80MPa·m 1 / 2 or 1.50~1.80MPa·m 1 / 2 In some embodiments, the fracture toughness may be 1.00 MPa·m 1 / 2 , 1.20MPa·m 1 / 2 , 1.30MPa·m 1 / 2 , 1.40MPa·m 1 / 2 , 1.50MPa·m 1 / 2 , 1.51MPa·m 1 / 2 , 1.57MPa·m 1 / 2 , 1.60MPa·m 1 / 2 , 1.64MPa·m 1 / 2 , 1.66MPa·m 1 / 2, 1.70MPa·m 1 / 2 , 1.80MPa·m 1 / 2 , 1.90MPa·m 1 / 2 or 2.00MPa·m 1 / 2 , or the fracture toughness within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0131] In some preferred embodiments of the present invention, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the tempered glass-ceramics is greater than 1.5 m, preferably greater than or equal to 1.80 m, more preferably 1.80 to 2.50 m, and more preferably 2.00 to 2.50 m; the average sandpaper drop resistance height is based on the test of at least 10 samples. In some embodiments, the average sandpaper drop resistance height may be 1.80 m, 2.00 m, 2.10 m, 2.20 m, 2.30 m, 2.40 m, or 2.50 m, or the average sandpaper drop resistance height is within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired performance of the present invention can be obtained.

[0132] In some preferred embodiments of the present invention, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper. If the glass sample does not break after falling, it is recorded as passed, and the pass rate of the tempered glass-ceramics is ≥50%, preferably ≥60%, more preferably ≥70%, and more preferably, the pass rate is 60% to 100%; the pass rate is based on the test of at least 10 samples. In some embodiments, the pass rate of the tempered glass-ceramics in the 2.5 m drop test (120-mesh sandpaper) can be 60%, 70%, 80%, 90% or 100%, or the pass rate of the 2.5 m drop test (120-mesh sandpaper) within the numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired performance of the present invention can be obtained.

[0133] In another preferred embodiment of the present invention, a drop and breakage test is performed on the tempered microcrystalline glass. Among the fragment particles generated when the tempered microcrystalline glass falls and breaks, the fragment particles whose longest side of the vertical projection on the two-dimensional drawing is greater than 5 mm account for more than 70% of the total weight of the glass, preferably more than 80%.

[0134] The drop and breakage test is conducted according to the test method of 120 mesh average drop resistance height. The glass is weighed before it falls and recorded as M1. After the glass falls and breaks, glass fragments are selected for sieving. A 4-mesh sieve (the aperture of the sieve is 5.16 mm) is used for sieving. The remaining glass fragments are weighed and recorded as M2. The proportion of fragments with the longest side of the vertical projection of the fragment particles on the two-dimensional drawing greater than 5 mm to the entire glass = M2 / M1.

[0135] After the glass fell and broke, the inventor took photos of the broken results and imported them into particle size analysis and calculation software (such as Nano measure) for analysis. During the analysis, glass fragments with a maximum vertical projection size greater than 1 mm were selected for marking, and the analysis and calculation software automatically calculated and output the maximum size average of the fragments with a maximum size greater than 1 mm. After the drop-resistant tempered microcrystalline glass with a safe stress state of the present invention fell and broke, the average maximum size of the fragments with a maximum vertical projection size greater than 1 mm among the glass fragments was greater than 5 mm.

[0136] In a second aspect, the present invention provides a chemically strengthened glass-ceramic, which is prepared from a substrate glass by heat treatment; the chemically strengthened glass-ceramic can obtain the above-mentioned strengthened glass-ceramic after chemical strengthening treatment; the chemically strengthened glass-ceramic contains spinel crystals, and the spinel crystals are the main crystalline phase of the glass-ceramic.

[0137] In the present invention, the composition of the chemically strengthened glass-ceramics can be obtained by semi-quantitative analysis using a fluorescent X-ray method, or can be measured by a wet analysis method such as ICP emission analysis.

[0138] It should be noted that, unless otherwise specified, the content of each component is expressed as a molar percentage based on the oxide.

[0139] After in-depth research, the inventors found that the existing spinel glass-ceramics containing only Na cannot reach a higher stress depth after chemical strengthening, has poor deep stress characteristics and poor drop resistance, mainly because the microstructure of the existing spinel glass-ceramics limits the depth of Na ions entering the interior of the glass, affecting the depth at which Na ions and K ions can be exchanged. The volume of [AlO4] tetrahedron is larger than that of [SiO4]. In theory, if the content of Al2O3 is increased, the ion exchange channel should be widened and the diffusion of Na ions should be promoted. However, the inventors found that a large increase in Al2O3 will greatly increase the difficulty of melting the substrate glass, especially in the absence of Li2O fluxing. Because the fluxing effect of Na2O is not as good as Li2O, but the melting difficulty of Al2O3 is greater than that of SiO2. By introducing a large amount of Na2O to exert the fluxing effect, crystallization will be uncontrollable, and the substrate glass will be ceramicized during the molding or annealing process.

[0140] In order to achieve a strengthened glass-ceramic that satisfies the above-mentioned crystallization characteristics and stress characteristics, the glass substrate composition and characteristics are as follows:

[0141] In order to obtain the drop-resistant strengthened microcrystalline glass with a safe stress state, and in order to obtain the strengthened microcrystalline glass with excellent drop resistance and safety performance, the inventors continuously adjust the formula, adjust the amount of each oxide in the formula and the amount relationship of each oxide, take into account the melting effect, optical effect, stress effect, drop resistance effect and safety performance, and provide a chemically strengthened microcrystalline glass with the following composition, which contains the following proportions of oxides in mol%: SiO238.00-48.00%, Al2O325.50-30.00%, ZrO23.00-5.00%, MgO 5.00-8.00%, ZnO8.00-14.00%, Na2O 7.20-14.00%, B2O33.00-8.00%, K2O 0~2.00% and Y2O30~1.00%; wherein the spinel glass-ceramics for chemical strengthening substantially does not contain Li2O, and in mol%, Li2O is less than 0.01%.

[0142] It should be understood that the composition of the substrate glass is the same as the composition of the chemically strengthened glass-ceramics of the present invention, measured in mol% of oxides. After the chemical strengthening ion exchange process, the composition at the surface of the glass-ceramics or substrate glass may be different from the composition of the newly formed glass-ceramics or substrate glass (i.e., the glass-ceramics or substrate glass that has not undergone ion exchange). That is, the composition of the compressive stress layer formed on the surface of the strengthened glass-ceramics by ion exchange may be different from the composition of the chemically strengthened glass-ceramics. This is because during ion exchange, one type of alkali metal ion (e.g., Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced by, such as Na in glass + K in strengthening salt bath + Exchange, K + Replaced by, and / or, Li in glass + and Na in the strengthening salt bath + Exchange, by Na + However, in the embodiment, the composition of the glass-ceramics or substrate glass at the center of the depth of the glass product or near the center of the depth still has the composition of the newly formed glass-ceramics or substrate glass. That is, in the present invention, the composition of the tensile stress layer of the strengthened glass-ceramics still has the composition of the chemically strengthened glass-ceramics described above.

[0143] Next, the range of each component (ingredient) of the chemically strengthened glass-ceramics of the present invention will be described.

[0144] The inventors have found that in the formula system of the present invention, the appropriate increase in the content of Na2O helps the chemical strengthening of microcrystalline glass to obtain higher stress characteristics, including high surface stress characteristics and high deep stress characteristics, and can also reduce the melting temperature and the temperature of crystal precipitation. If the content of Na2O is too low, it is not only not conducive to strengthening microcrystalline glass to obtain high stress characteristics, but also leads to an increase in the heat treatment temperature, increasing the difficulty of mass production of microcrystalline glass, and during the heat treatment process, it is also easy to cause direct phase separation or precipitation of impurities that affect the optical properties of microcrystalline glass, resulting in translucent or even opaque microcrystalline glass. The excessive addition of Na2O will affect the network structure of the glass due to the provision of a large amount of free oxygen, and it is also easy to cause the ceramicization of the substrate glass during the annealing process or the precipitation of impurities that affect the optical properties of the microcrystalline glass during the heat treatment of the substrate glass to prepare microcrystalline glass, so that the transmittance of the obtained microcrystalline glass decreases. Therefore, in the present invention, the content of Na2O is 7.20-14% in mol%, preferably 7.20-13%, and more preferably 7.20-12.00%.

[0145] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain 7.20-13.50%, 7.20-13.00%, 7.20-12.50%, 7.20-12.00%, 7.20-11.50%, 7.20-11.00%, 7.20-10.50%, 7.20 ~10.00%, 7.20~9.50%, 7.20~9.00%, 7.70~14.00%, 8.20~14.00%, 8.70~14.00%, 9.20~14.00%, 9.20~14.00%, 10.20~14.00%, 10.70~14.00% or 11.50~14.00% Na2O. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain Na2O in a molar percentage of 7.20%, 7.70%, 8.20%, 8.70%, 9.20%, 9.70%, 10.20%, 10.70%, 11.20%, 11.50%, 12.20%, 12.70%, 13.20%, 13.70% or 14.00%, or in a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0146] The inventors have found that SiO2 is a glass network forming oxide and an indispensable component of the glass network structure. Properly increasing the content of SiO2 can increase the stability and mechanical strength of the glass, but excessive SiO2 will increase the viscosity of the base glass, making it more difficult to melt the glass, thereby reducing the formability of the base glass. Therefore, in the present invention, the content of SiO2 is 38.00-48.00% in mol%, preferably 38.00-44.00%.

[0147] In some embodiments, the tensile stress layer of the above-mentioned strengthened microcrystalline glass or the microcrystalline glass for chemical strengthening or the substrate glass may contain SiO2 with a molar percentage of 40.00% to 48.00%, 42.00% to 48.00%, 44.00% to 48.00%, 46.00% to 48.00%, 38.00% to 46.00%, 38.00% to 44.00%, 38.00% to 42.00% or 38.00% to 40.00%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain SiO2 with a molar percentage of 38.00%, 38.50%, 39.00%, 40.00%, 41.00%, 42.00%, 43.00%, 44.00%, 45.00%, 46.00%, 47.00% or 48.00%, or within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0148] The inventors have found that in the formula system of the present invention, the appropriate addition of Al2O3 can not only promote the precipitation of the main crystal phase spinel, inhibit the precipitation of other impurities such as quartz ss that affect the optical properties of the microcrystalline glass of the present system, but also increase the ion exchange rate during the strengthening process and promote the ion exchange. However, too much Al2O3 will cause the melting difficulty of the substrate glass to increase sharply, and at the same time accelerate the crystallization rate of the substrate glass, so that the substrate glass is prone to crystallization and devitrification during the normal cooling process during preparation. Therefore, in the present invention, the Al2O3 content is 25.50-30.00% in mol%, preferably 25.50-28.00%.

[0149] In some embodiments, the tensile stress layer of the above-mentioned strengthened microcrystalline glass or the microcrystalline glass for chemical strengthening or the substrate glass may contain Al2O3 with a molar percentage of 25.50-29.50%, 25.50-29.00%, 25.50-28.50%, 25.50-28.00%, 25.50-27.50%, 25.50-27.00%, 25.50-26.50%, 26.00-30.00%, 26.50-30.00%, 27.00-30.00%, 27.50-30.00%, 28.00-30.00%, 28.50-30.00% or 29.00-30.00%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain Al2O3 in a molar percentage of 25.50%, 26.00%, 26.50%, 27.00%, 27.50%, 28.00%, 28.50%, 29.00%, 29.50% or 30.00%, or in a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0150] The inventors have found that in the formula system of the present invention, MgO and ZnO, as the main components of spinel, can promote the precipitation of spinel when added in appropriate amounts, and can also reduce the difficulty of melting the substrate glass to a certain extent. However, the addition of excessive MgO and ZnO often causes the spinel grains to grow very easily, and it is difficult to obtain microcrystalline glass with high transparency. That is, the content relationship of MgO and ZnO largely determines whether the microcrystalline glass sample can be transparent and whether the optical properties are excellent. Therefore, in the present invention, in terms of mol%, the MgO content is 5.00% to 8.00%, preferably 5.00 to 7.00%, and more preferably 5.00 to 6.50%; the ZnO content is 8.00% to 14.00%, preferably 8.00 to 12.00%, and more preferably 8.00 to 10.50%.

[0151] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain MgO in a molar percentage of 5.50% to 8.00%, 6.00% to 8.00%, 6.50% to 8.00%, 7.00 to 8.00%, 5.00% to 7.50%, 5.00% to 7.00%, 5.00% to 6.50% or 5.00% to 6.00%. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0152] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain a molar percentage of 8.50% to 14.00%, 9.00% to 14.00%, 9.50% to 14.00%, 10.00 to 14.00%, 10.50 to 14.00%, 11.00 to 14.00%, 11.50 to 14.00%, 12.00 to 14.00%, 8.00 to 13.50, 8.00 to 13.00, 8.00 to 12.50, 8.00 to 12.00, 8.00 to 11.50, 8.00 to 11.00, 8.00 to 10.50 or 8.00 to 10.00% ZnO. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain ZnO in a molar percentage of 8.00%, 8.50%, 9.00%, 9.50%, 10.00%, 10.50%, 11.00%, 11.50%, 12.00%, 12.50%, 13.00%, 13.50% or 14.00%, or in a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0153] The inventors have found that in the formula system of the present invention, ZrO2 acts as an effective nucleating agent. When the substrate glass is heat-treated to prepare the microcrystalline glass, ZrO2 is first precipitated from the glass in the form of crystals, and the ZrO2 crystals become crystal nuclei for the subsequent growth of the main crystal spinel. Within a certain glass composition range, the content of ZrO2 will affect the formation of the substrate glass, the crystal shape, crystal type and crystal size of the microcrystalline glass after the substrate glass is heat-treated. Therefore, in the present invention, the ZrO2 content is 3.00-5.00% in mol%, preferably 3.00-4.00%.

[0154] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or substrate glass may contain ZrO2 with a molar percentage of 3.50-5.00%, 4.00-5.00%, 4.50-5.00%, 3.00-4.50%, 3.00-4.00% or 3.00-3.50%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or substrate glass may contain ZrO2 with a molar percentage of 3.00%, 3.50%, 4.00%, 4.50% or 5.00%, or within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0155] The inventors have found that in the formula system of the present invention, an appropriate amount of B2O3 can not only greatly reduce the difficulty of melting the substrate glass, but also help promote the precipitation of the main crystal phase spinel. When the amount of B2O3 added is too low, it is easy to cause melting defects during the preparation of the substrate glass. However, the addition of excessive B2O3 can easily lead to opacity in the glass when the substrate glass is heat-treated to prepare microcrystalline glass. At the same time, it may cause the precipitation of other impurity crystal phases, seriously affecting the transparency of the microcrystalline glass. Therefore, in the present invention, the content of B2O3 is 3.00-8.00% in mol%, preferably 3.00-7.00%, and more preferably 3.00-6.50%.

[0156] In some embodiments, the tensile stress layer of the above-mentioned strengthened microcrystalline glass or the microcrystalline glass for chemical strengthening or the substrate glass may contain B2O3 with a molar percentage of 3.50-8.00%, 4.00-8.00%, 4.50-8.00%, 5.00-8.00%, 5.50-8.00, 6.00-8.00%, 6.50-8.00%, 7.00-8.00%, 3.00-7.50%, 3.00-7.00%, 3.00-6.50%, 3.00-6.00%, 3.00-5.50%, 3.00-5.00%, 3.00-4.50% or 3.00-4.00%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain B2O3 in a molar percentage of 3.00%, 3.50%, 4.00%, 4.50%, 5.00%, 5.50%, 6.00%, 6.50%, 7.00%, 7.50% or 8.00%, or in a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0157] In order to ensure the melting effect and optical properties of the glass, the content of Na2O+B2O3 is 10.20-20.00%, preferably 10.20-18.00%. The coordination of N2O+B2O3 with the overall composition can solve the melting problem while enabling the base glass to obtain better optical properties. At the same time, the increase of Na2O and B2O3 can synergistically solve the melting problem caused by the increase of Al2O3 content.

[0158] The inventors have found that in the formula system of the present invention, although BaO can improve the melting effect of the base glass and inhibit the growth of grains to a certain extent, thereby improving the optical properties of the microcrystalline glass, it has a strong inhibitory effect on the Na-K exchange, which is not conducive to the chemical strengthening of the microcrystalline glass. Therefore, it is preferably not added in the present invention, and the BaO content is less than 0.01% in mol%.

[0159] The inventors have found that in the formulation system of the present invention, the addition of TiO2 as a nucleating agent will cause the substrate glass to have an undesirable color. In order to obtain the desired transparent colorless microcrystalline glass, the present invention preferably does not contain TiO2, and the TiO2 content is less than 0.01% in mol%.

[0160] The inventors have found that in the formulation system of the present invention, K2O is an optional component that helps to improve the low temperature melting property and formability of the glass. + Radius larger than Na + , adding K2O in proper amount can reduce the tendency of glass to crystallize and increase the transparency and gloss of glass. However, if K2O is contained in excessive amount, it is not only easy to reduce the chemical stability and hardness of glass, but also easy to make the crystallization ability of glass stronger, glass is easy to lose transparency, and crystallized glass is easy to break. Therefore, in the present invention, the content of K2O is 0-2% in mol%.

[0161] The inventors have found that in the formula system of the present invention, Y2O3 is an optional component that improves the hardness and chemical stability of glass ceramics and inhibits the crystallization of glass forming. An appropriate amount of Y2O3 can improve the density of the glass phase, thereby improving the overall strength of the microcrystalline glass. At the same time, it can form a eutectic with ZrO2, reducing the unevenness caused by ZrO2 precipitation when melting in the furnace. However, when the Y2O3 content is too high, it will affect the precipitation of spinel crystals and reduce the chemical strengthening properties of glass and glass ceramics. Therefore, in the present invention, the Y2O3 content ranges from 0 to 1% in mol%.

[0162] In some preferred embodiments of the present invention, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass composition of the present invention satisfies the following conditions, based on the content of each component expressed in molar percentage in the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass composition:

[0163] The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.18, and the preferred value of A is 0.05 to 0.15.

[0164] (1)A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3;

[0165] and / or,

[0166] The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.80, and the preferred value of B is 0.60 to 0.78.

[0167] (2)B=3.8×Na2O+B2O3+4.5×MgO+6.0×ZnO-0.4×Al2O3-SiO2.

[0168] The inventors have discovered through experimental studies that the A value calculated based on the above formula is closely related to the melting effect of the substrate glass used to prepare the strengthened glass-ceramics or chemically strengthened glass-ceramics. By controlling the A value within an appropriate range through the specific proportional relationship of the above-mentioned oxide components, it can be ensured that a transparent substrate glass that meets the requirements is obtained, and that the oxide components in the substrate glass are completely melted without any unmelted components.

[0169] The inventors have also discovered through experiments that the B value calculated based on the above formula is closely related to the melting effect of the substrate glass used to prepare the strengthened microcrystalline glass or chemically strengthened microcrystalline glass. By controlling B within an appropriate range through the specific proportion of the above-mentioned oxide components, it can be ensured that the substrate glass will not be ceramicized during the preparation process, especially during the annealing process, thereby ensuring that a transparent substrate glass that meets the requirements is obtained.

[0170] In some embodiments, the A value may be 0.07-0.15, 0.09-0.15, 0.11-0.15, 0.13-0.15, 0.05-0.13, 0.05-0.11, 0.05-0.09 or 0.05-0.07. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may include an A value of 0.05, 0.07, 0.09, 0.11, 0.13, 0.15, 0.17 or 0.18, or an A value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges as long as the glass having the desired performance of the present invention can be obtained.

[0171] In some embodiments, the B value may be 0.60-0.76, 0.60-0.74, 0.60-0.72, 0.60-0.70, 0.60-0.68, 0.60-0.64, 0.62-0.78, 0.64-0.78, 0.66-0.78, 0.68-0.78, 0.70-0.78, 0.72-0.78 or 0.74-0.78. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may include a B value of 0.60, 0.62, 0.64, 0.66, 0.68, 0.70, 0.72, 0.74, 0.76, 0.78 or 0.80, or a B value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0172] In some preferred embodiments of the present invention, in the tensile stress layer of the above-mentioned strengthened microcrystalline glass-ceramics or the chemically strengthened microcrystalline glass-ceramics or the substrate glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: the molar percentage of Al2O3 minus the molar percentage of MgO and the molar percentage of ZnO is 8.00-15.00%, that is, Al2O3-MgO-ZnO is 8.00-15.00%. Al2O3, MgO and ZnO are all main components of the main crystal phase spinel crystal of the present invention. The present invention can ensure the acquisition of microcrystalline glass with high crystal content / crystallinity by adjusting the content relationship of Al2O3, MgO and ZnO, which is beneficial to improve the intrinsic strength of the microcrystalline glass. On the other hand, by leaving an appropriate amount of Al2O3 in the residual glass phase, a

[0173] The [AlO4] tetrahedral structure is also more conducive to the chemical strengthening of microcrystalline glass and to the strengthening of microcrystalline glass to obtain high stress characteristics. Because the volume of [AlO4] tetrahedron is larger than that of [SiO4], the presence of an appropriate amount of [AlO4] is more conducive to broadening ion exchange channels and promoting the diffusion of alkali metal ions.

[0174] In some embodiments, the value of Al2O3-MgO-ZnO may be 8.50-15.00%, 9.00-15.00%, 9.50-15.00%, 10.00-15.00%, 10.50-15%, 11.00-15.00%, 11.50-15.00%, 12.00-15.00%, 12.50-15%, 13.00-15.00%, 13.50-15.0 0%, 14.00-15.00%, 8.00-14.50%, 8.00-14.00%, 8.00-13.50%, 8.00-13.00%, 8.00-12.50%, 8.00-12.00%, 8.00-11.50%, 8.00-11.00%, 8.00-10.50%, 8.00-10.00%, 8.00-9.50% or 8.00-9.00%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain Al2O3-MgO-ZnO at a value of 8.00%, 8.50%, 9.00%, 9.50%, 10.00%, 10.50%, 11.00%, 11.50%, 12.00%, 12.50%, 13.00%, 13.50%, 14.00%, 14.50% or 15.00%, or a value of Al2O3-MgO-ZnO within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0175] In another preferred embodiment of the present invention, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass composition of the present invention satisfies the following requirements, based on the content of each component expressed by mole percentage in the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass composition:

[0176] The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%, preferably 34.00 to 46.00%.

[0177] (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3);

[0178] and / or,

[0179] The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%, preferably 60.00 to 75.00%.

[0180] (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

[0181] The inventors have found through experimental research that the X value calculated based on the above formula is closely related to the deep stress depth of the drop-resistant tempered glass-ceramics with a safe stress state. By controlling X within a suitable range through the specific proportional relationship of the above-mentioned oxide components, it can be ensured that the tempered glass-ceramics prepared by the chemically strengthened glass-ceramics of the present invention obtains excellent deep stress characteristics, such as high CS_50, DOL_O, |CT_AV|, |CT_CV|, and CT_LD values.

[0182] The inventors have also discovered through experimental studies that the Y value calculated based on the above formula is closely related to the surface stress characteristics of the tempered glass-ceramics with excellent anti-drop performance. By controlling the Y value within an appropriate range through the specific proportional relationship of the above-mentioned oxide components, it can be ensured that the tempered glass-ceramics prepared by the chemically strengthened glass-ceramics of the present invention obtains excellent surface stress characteristics, such as a high surface K2O concentration and a high surface CS value.

[0183] In some embodiments, the value of X can be 32.00-50.00%, 34.00-50.00%, 36.00-50.00%, 38.00-50.00%, 40.00-50.00%, 42.00-50.00%, 44.00-50.00%, 46.00-50.00%, 30.00-48.00%, 30.00-46.00%, 30.00-44.00%, 30.00-42.00%, 30.00-40.00%, 30.00-38.00%, 30.00-36.00%, or 30.00-34.00%. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics or substrate glass may include an X value of 30.00%, 32.00%, 34.00%, 36.00%, 38.00%, 40.00%, 42.00%, 44.00%, 46.00%, 48.00% or 50.00%, or an X value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0184] In some embodiments, the Y value can be 62.00-80.00%, 64.00-80.00%, 66.00-80.00%, 68.00-80.00%, 70.00-80.00%, 72.00-80.00%. 74.00-80.00%, 76.00-80.00%, 60.00-78.00%, 60.00-76.00%, 60.00-74.00%, 60.00-72.00%, 60.00-70.00%, 60.00-68.00%, 60.00-66.00% or 60.00-64.00%. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics or substrate glass may include a Y value of 60.00%, 62.00%, 64.00%, 66.00%, 68.00%, 70.00%, 72.00%, 74.00%, 76.00%, 78.00% or 80.00%, or a Y value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0185] In some preferred embodiments of the present invention, the spinel crystal is a zinc-magnesium spinel solid solution (Zn, Mg)Al2O4, that is, the main crystalline phase of the chemically strengthened glass-ceramics or strengthened glass-ceramics of the present invention is (Zn, Mg)Al2O4; and / or, the chemically strengthened glass-ceramics or strengthened glass-ceramics of the present invention also include a secondary crystalline phase of tetragonal zirconia. (Zn, Mg)Al2O4 has a high Young's modulus and shear modulus, which is beneficial to improving the intrinsic strength of the chemically strengthened glass-ceramics or strengthened glass-ceramics of the present invention, such as making the strengthened glass-ceramics have high hardness, strength, fracture toughness, etc.

[0186] It should be understood that the strengthened microcrystalline glass of the present invention is obtained by chemically strengthening the above-mentioned chemically strengthened microcrystalline glass provided by the present invention, and in the chemically strengthened microcrystalline glass of the present invention, the main crystal phase is (Zn, Mg)Al2O4, and the secondary crystal phase includes tetragonal ZrO2. The crystal phase does not contain alkali metals and does not participate in ion exchange. Therefore, the crystal phase composition does not change basically before and after strengthening, and the optical properties of the microcrystalline glass, such as transmittance and optical b value, also do not change basically.

[0187] In some preferred embodiments of the present invention, the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention have good crystallinity, for example, the crystallinity of the strengthened glass-ceramics or chemically strengthened glass-ceramics is above 20wt%; preferably, the crystallinity is 20.00-50.00wt%; further preferably, the crystallinity is 30.00-50.00wt%; more preferably, the crystallinity is preferably 35-45wt%. High crystallinity / crystal content can give the glass-ceramics higher intrinsic strength, so that the chemically strengthened microcrystals of the present invention have excellent mechanical properties.

[0188] In some embodiments, the crystallinity of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 22.00-50.00wt%, 24.00-50.00wt%, 26.00-50.00wt%, 28.00-50.00wt%, 30.00-50.00wt%, 32.00-50.00wt%, 34.00-50.00wt%, 36.00-50.00wt%, 38.00-50.00wt%, 40.00-50.00wt%, 42.00-50.00wt%, 44.00-50.00wt%. wt%, 46.00~50.00wt%, 20.00~48.00wt%, 20.00~46.00wt%, 20.00~44.00wt%, 20.00~42.00wt%, 20.00~40.00wt%, 20.00~38.00wt %, 20.00~36.00wt%, 20.00~34.00wt%, 20.00~32.00wt%, 20.00~30.00wt%, 20.00~28.00wt%, 20.00~26.00wt% or 20.00~24.00wt%. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics may include a crystallinity value of 20.00wt%, 22.00wt%, 24.00wt%, 26.00wt%, 28.00wt%, 30.00wt%, 32.00wt%, 34.00wt%, 36.00wt%, 38.00wt%, 40.00wt%, 42.00%, 44.00wt%, 46.00wt%, 48.00wt% or 50.00wt%, or a crystallinity value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0189] In some preferred embodiments of the present invention, the average grain size of the strengthened glass-ceramics or chemically strengthened glass-ceramics is ≤15.0 nm, preferably 1.0 to 15.0 nm, more preferably 1.0 to 10.0 nm, and more preferably 4.5 to 8.0 nm. Appropriate grain size is conducive to achieving excellent optical effects of the glass-ceramics.

[0190] In some embodiments, the average grain size of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 1.0-13.0 nm, 1.0-11.0 nm, 1.0-9.0 nm, 1.0-7.0 nm, 1.0-5.0 nm, 1.0-3.0 nm, 3.0-15.0 nm, 3.0-13.0 nm, 3.0-11.0 nm, 3.0-9.0 nm, 3.0-7.0 nm or 3.0-5.0 nm. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics may include an average grain size value of 1.0 nm, 3.0 nm, 4.5 nm, 5.0 nm, 7.0 nm, 8.0 nm, 9.0 nm, 11.0 nm, 13.0 nm or 15.0 nm, or an average grain size value within a numerical range consisting of any two of the above specific numerical values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0191] In another preferred embodiment of the present invention, the above-mentioned strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention exhibits high transparency in the visible light range (that is, the drop-resistant strengthened glass-ceramics with a safe stress state is transparent). Strengthened glass-ceramics or chemically strengthened glass-ceramics exhibit high transmittance in the visible light range. For example, the above-mentioned chemically strengthened glass-ceramics, at a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened glass-ceramics is greater than or equal to 85%, and preferably the transmittance is greater than or equal to 89%.

[0192] In some embodiments, at a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 89.0%, 89.5%, 90.0%, 90.5% or 91.0%, or a transmittance within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired performance of the present invention can be obtained.

[0193] In some preferred embodiments of the present invention, the Young's modulus of the above-mentioned strengthened glass-ceramics or chemically strengthened glass-ceramics is ≥100 GPa, preferably ≥110 GPa, and more preferably 114 GPa≤Young's modulus≤140 GPa. It should be understood that in the present invention, after chemical strengthening treatment, the Young's modulus of the chemically strengthened glass-ceramics will increase appropriately, that is, the Young's modulus of the strengthened glass-ceramics will be greater than or equal to the chemically strengthened glass-ceramics.

[0194] In some embodiments, the Young's modulus of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention can be 114-140 GPa, 114-138 GPa, 114-136 GPa, 114-134 GPa, 114-132 GPa, 114-130 GPa, 114-128 GPa, 114-126 GPa, 116-140 GPa, 118-140 GPa, 120-140 GPa, 122-140 GPa, 124-140 GPa, 126-140 GPa or 128-140 GPa. In some embodiments, the Young's modulus of the strengthened glass-ceramics or chemically strengthened glass-ceramics may be 114 GPa, 116 GPa, 118 GPa, 120 GPa, 122 GPa, 240 GPa, 126 GPa, 128 GPa, 130 GPa, 135 GPa or 140 GPa, or a Young's modulus value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0195] In some preferred embodiments of the present invention, the optical b value of the strengthened glass-ceramics or chemically strengthened glass-ceramics is 0.20 to 1.50, preferably 0.50 to 1.20, at a thickness of 0.7 mm.

[0196] In some embodiments, at a thickness of 0.7 mm, the optical b value of the above-mentioned strengthened microcrystalline glass or chemically strengthened microcrystalline glass of the present invention can be 0.20-1.40, 0.20-1.30, 0.20-1.20, 0.20-1.10, 0.20-1.00, 0.20-0.90, 0.20-0.80, 0.20-0.70, 0.20-0.40, 0.30-1.50, 0.40-1.50, 0.50-1.50, 0.60-1.50, 0.70-1.50, 0.80-1.50, 0.90-1.50, 1.00-1.50 or 1.10-1.50. In some embodiments, the optical b value of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40 or 1.50, or an optical b value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0197] In a third aspect, the chemically strengthened glass-ceramics can be produced and manufactured by the following method: heat treating the substrate glass to form the above-mentioned chemically strengthened glass-ceramics; the chemically strengthened glass-ceramics contain spinel crystals, and the spinel crystals are the main crystalline phase of the chemically strengthened glass-ceramics; the composition of the chemically strengthened glass-ceramics contains the following proportions of oxides in mol%: SiO238.00~48.00%, Al2O325.50~30.00%, ZrO23.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na2O 7.20~14.00%, B2O33.00~8.00%, K2O 0~2.00% and Y2O30~1.00%; wherein the chemically strengthened glass-ceramics basically does not contain Li2O, and in mol%, Li2O is less than 0.01%.

[0198] Exemplarily, the method for preparing the chemically strengthened glass-ceramics of the present invention may include the following steps:

[0199] (1) preparing a substrate glass: the substrate glass contains the following oxides in mol% ratio: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%; wherein the substrate glass substantially does not contain Li2O, and Li2O, in mol%, is less than 0.01%;

[0200] (2) Preparation of glass-ceramics: The substrate glass obtained in step (1) is heat-treated to obtain glass-ceramics for chemical strengthening.

[0201] In the present invention, the molding method of the substrate glass includes but is not limited to float, overflow, rolling or casting process. Exemplarily, the components are mixed evenly according to the formula, and after melting and molding, they are cooled and annealed to obtain the substrate glass. Preferably, the mixed raw materials are placed in an electric furnace or a gas furnace, and melted at a melting temperature of 1250°C to 1650°C, more preferably at a melting temperature of 1480°C to 1650°C, and the melting time is 5 to 24 hours; after the melting treatment is completed, the glass liquid is cast into a mold for molding, and after cooling to 850°C to 1000°C, it is preferably placed in an annealing furnace for annealing, and the annealing temperature is 500°C to 650°C, and the annealing is kept warm for 12 to 48 hours.

[0202] The heat treatment in step (2) may include a nucleation treatment and / or a crystallization treatment, and preferably a nucleation treatment and a crystallization treatment are used.

[0203] In order to obtain the desired physical properties of the chemically strengthened glass-ceramics, the substrate glass can be heat treated in one step or in two or more steps. If a one-step heat treatment is performed, it means that the nucleation treatment is not performed separately, and the nucleation and target crystal growth are directly performed in a one-step heating process, which can be understood as a direct crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, first a nucleation treatment, i.e., a nucleation treatment, is performed, and then a target crystal growth treatment, i.e., a crystallization treatment, is performed.

[0204] It should be understood that in the present invention, the nucleation treatment is to increase the temperature to a prescribed nucleation treatment temperature (also called nucleation temperature), and after reaching the nucleation treatment temperature, maintain the temperature for a certain time (i.e., nucleation treatment time, also called nucleation time). The crystallization treatment is to increase the temperature to a prescribed crystallization treatment temperature (also called crystallization temperature), and after reaching the crystallization treatment temperature, maintain the temperature for a certain time (i.e., crystallization treatment time, also called crystallization time).

[0205] In order to make the chemically strengthened glass-ceramics precipitate the desired crystal phase and obtain the desired physical and chemical properties, the preferred heat treatment process of the present invention is:

[0206] The nucleation temperature is preferably 600-800° C., and the nucleation treatment time can be 0-72 h, preferably 0-24 h; the crystallization treatment temperature is 700-1000° C., and the crystallization treatment time is 0.1-72 h, preferably 0.1-24 h.

[0207] It is worth mentioning that the inventors found through a large number of experiments that due to the optimization of the formula of the present invention, the desired target microcrystalline glass can be prepared at a heat treatment temperature lower than that of the existing scheme. Therefore, in the present invention, the temperature of the nucleation treatment may be preferably 600-750°C; the temperature of the crystallization treatment may be preferably 700-800°C, which is more conducive to improving the mass production performance of microcrystalline glass and is more in line with the industry's development needs of energy conservation and carbon reduction.

[0208] In some preferred embodiments of the present invention, a two-step temperature rise heat treatment method is used to prepare the chemically strengthened microcrystalline glass, that is, the substrate glass is subjected to a nucleation treatment and a crystallization treatment in sequence to prepare the microcrystalline glass. In some embodiments, when the temperature of the nucleation treatment is 600-750°C, the nucleation treatment is preferably 60-360 minutes, and the nucleation time is preferably 100-300 minutes. And / or, when the temperature of the crystallization treatment is 700-800°C, the crystallization time is preferably 60-360 minutes, and the crystallization time is more preferably 100-300 minutes.

[0209] In some preferred embodiments of the present invention, during heat treatment, the heating rate is controlled to be 5 to 15 K / min, preferably 10 K / min. It should be understood that the heating rate here includes the heating rate from room temperature to nucleation temperature and the heating rate from nucleation temperature to crystallization temperature.

[0210] In some preferred embodiments of the present invention, the composition of the substrate glass, expressed in terms of the content expressed in molar percentage of oxides, satisfies:

[0211] A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3, A≤0.18, preferably the value of A is 0.05~0.15;

[0212] and / or, B = 3.8 × Na2O + B2O3 + 4.5 × MgO + 6.0 × ZnO - 0.4 × Al2O3 - SiO2, B ≤ 0.80, preferably the value of B is 0.60 to 0.78;

[0213] and / or, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3), X=30.00-50.00%, preferably X=34.00-46.00%;

[0214] and / or, Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3), Y=60.00-80.00%, preferably Y=60.00-75.00%;

[0215] And / or, in the substrate glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

[0216] In some preferred embodiments of the present invention, the substrate glass contains substantially no BaO, and the BaO content is less than 0.01% in mol%; and / or the substrate glass contains substantially no TiO2, and the TiO2 content is less than 0.01% in mol%.

[0217] In the present invention, the microcrystalline glass obtained in the above step (2) can be subjected to cold working treatment as needed. The cold working treatment is to process the microcrystalline glass into microcrystalline glass samples. For example, the microcrystalline glass is processed into a polished sheet of a desired size by one or more methods of slicing, grinding, and polishing, such as a polished sheet with a length, width, and thickness of 50 mm × 50 mm × 0.7 mm.

[0218] In the present invention, those skilled in the art can select the thickness of the microcrystalline glass according to the requirements. Exemplarily, the thickness of the microcrystalline glass is 0.2-5.0 mm.

[0219] In the present invention, when preparing the substrate glass, a clarifier can be added to the raw materials for preparing the substrate glass, and the clarifier includes but is not limited to the raw materials for preparing the substrate glass in the above-mentioned step of preparing the substrate glass. The clarifier includes but is not limited to one or more of NaCl, Na2SO4, SnO2, As2O3, Sb2O3, NaNO3, KNO3, CeO2 and (NH4)2SO4; preferably one or more of NaCl, SnO2, NaNO3 and CeO2. Based on the total mass of the raw materials of the substrate glass, the amount of the clarifier added is 0.01wt% to 2.00wt%, preferably 0.01wt% to 1.50wt%.

[0220] In a fourth aspect, the present invention further provides a method for preparing a strengthened glass-ceramic, comprising the following steps: subjecting the above-mentioned glass-ceramic for chemical strengthening to chemical strengthening treatment to obtain the above-mentioned strengthened glass-ceramic, wherein the strengthened glass-ceramic comprises spinel crystals, and the spinel crystals are the main crystalline phase of the strengthened glass-ceramic; the composition of the strengthened glass-ceramic substantially does not contain Li2O; the strengthened glass-ceramic satisfies: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t; eXp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2)<1.30;

[0221] Wherein, t is the thickness of the glass-ceramic in μm, DOL_0 is in μm, and |CT_CV| and |CT_AV| are in MPa.

[0222] In the present invention, the chemical strengthening treatment includes a single-step strengthening method or a multi-step strengthening method; and the salt bath for the chemical strengthening treatment is a molten salt containing a potassium salt.

[0223] In some embodiments, the chemically strengthened glass-ceramics may be processed into sheets and / or shaped (such as punching, hot bending, etc.), polished and / or swept after shaping, and then chemically strengthened through a chemical strengthening process.

[0224] The chemical strengthening treatment described in the present invention is an ion exchange method. During the ion exchange process, the smaller alkali metal ions in the chemically strengthened glass-ceramics are replaced or "exchanged" by larger alkali metal ions of the same valence state near the glass-ceramics, and the larger ions replace the smaller ions, thereby constructing a compressive stress layer in the glass. The ion exchange strengthening method can be carried out in multiple steps, such as two steps, or in a single step. Ion exchange is carried out by immersing the chemically strengthened glass-ceramics in a salt bath of at least one molten salt containing larger alkali metal ions, so that the larger alkali metal ions in the salt bath are used to replace the smaller alkali metal ions in the glass-ceramics. Alternatively, other monovalent metal ions such as Ag + , Tl + , Cu + etc. can also be used to exchange monovalent ions. The ion exchange process may include, but is not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths of the same or different compositions, with washing and / or annealing steps between immersions.

[0225] In some preferred embodiments of the present invention, the concentration of potassium salt in the salt bath for chemical strengthening treatment is 60wt% to 100wt%. For example, the salt bath containing potassium salt can be 100wt% potassium nitrate, or a mixed salt of potassium nitrate and sodium nitrate, and the concentration of potassium nitrate in the mixed salt is greater than or equal to 60wt% and less than 100wt%. In addition, 0 to 1wt% LiNO3 can be added to the salt bath as needed based on the mass of the salt bath. Preferably, the temperature of the salt bath for chemical strengthening treatment is 380℃ to 600℃, preferably 400℃ to 550℃.

[0226] In some embodiments, the chemically strengthened glass-ceramics can be ion exchanged in a mixed molten salt composed of 0-20wt% NaNO3 and 80-100wt% KNO3, preferably the molten salt / salt bath temperature is 380°C to 600°C, preferably 430°C to 550°C, preferably 450°C to 530°C, and further preferably, the ion exchange time is 4 to 48 hours, preferably 9 to 48 hours. In this embodiment, the K ions in the molten salt / salt bath will replace part of the Na ions in the chemically strengthened glass-ceramics, thereby forming a compressive stress layer at the surface of the glass to obtain a strengthened glass-ceramics, so that the chemically strengthened glass-ceramics achieves a specific stress distribution structure, giving the chemically strengthened glass-ceramics specific and excellent surface stress characteristics and deep stress characteristics, thereby giving it high mechanical properties and safety performance. Furthermore, it is preferred that the molten salt / salt bath temperature is 450-500° C. and the ion exchange time is 22-48 hours, or the molten salt / salt bath temperature is 510-530° C. and the ion exchange time is 9-12 hours.

[0227] In some embodiments, the above-mentioned chemically strengthened microcrystalline glass can be chemically strengthened by a multi-step method. In the first step, ion exchange is carried out in a mixed molten salt composed of NaNO3 with a NaNO3 content (wt%) of 0 to 20% and 80-100wt% KNO3, and the molten salt / salt bath temperature is preferably 450-500°C, and the ion exchange time is preferably 22-48 hours; in the second step, ion exchange is carried out in a molten salt composed of 100wt% KNO3, and the molten salt / salt bath temperature is preferably 460-530°C, and the ion exchange time is preferably 1-5 hours.

[0228] In some embodiments, before the chemical strengthening treatment, the chemically strengthened glass-ceramics may be preheated at 300 to 400° C. as required, and the preheating time is preferably 10 to 30 minutes.

[0229] In some embodiments, a thermal migration process at 350-500° C. may be performed between multiple strengthening steps as needed, and the thermal migration time is preferably 15-120 min.

[0230] In some embodiments, in the single-step strengthening or multi-step strengthening, after continuously strengthening multiple batches of samples in each salt bath, when the surface CS of a batch of samples drops to 10-20% of the initial batch, the glass strengthening in the salt bath is stopped, and the salt bath needs to be cleaned or replaced for glass strengthening.

[0231] In a fifth aspect, the above-mentioned strengthened microcrystalline glass or the above-mentioned chemically strengthened microcrystalline glass or the above-mentioned substrate glass for preparing chemically strengthened microcrystalline glass provided by the present invention can be applied to mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

[0232] The following describes in detail how to prepare a tempered microcrystalline glass with excellent anti-drop performance and the beneficial effects achieved through examples and comparative examples.

[0233] 1: Specific operation examples

[0234] Example 1

[0235] According to the component proportions of glass formula 1 of Example 1 in Table 1, various raw materials (conventional industrial raw materials) are prepared in a platinum crucible, and the total amount of raw materials configured is 1000 g. Then, a V-type mixer is used to mix for 30 minutes. After mixing, 5 g of clarifier NaCl is added. Then, the raw materials are transferred to a platinum crucible, and then melted in a 1650°C lifting furnace (lifting furnace model: SJF1750, manufacturer: Nanjing Boyuntong Instrument Technology Co., Ltd.) for 5 hours, and then poured into a stainless steel mold preheated at 300°C (usually preheated to 200-400°C) for molding and cooling, cooled to 900°C, and then placed in a 600°C annealing furnace for annealing for 24 hours, and then cooled to room temperature with the furnace to obtain the substrate glass.

[0236] The substrate glass is heat treated in a resistance furnace (equipment model: SLX1400-40, manufacturer: Shanghai Shengli Testing Instrument Co., Ltd.), and the heat treatment process (nucleation temperature / nucleation time, crystallization temperature / nucleation time, and heating rate during heat treatment) is carried out according to Table 1 to obtain a microcrystalline glass sample brick for chemical strengthening. The microcrystalline glass sample brick is cut, CNC processed (computer numerical control, i.e., numerical control machine tool, the CNC instrument model used in the present invention is: RCG500S), and polished to obtain the mirror-smooth microcrystalline glass sheet. In the present invention, the length, width, and thickness of the processed microcrystalline glass sheet are samples with specifications of 50mm×50mm×0.7mm.

[0237] The physical properties of the prepared glass-ceramics were tested according to the following method:

[0238] Young's modulus test: The Young's modulus of the sample was obtained by ultrasonic testing, and the instrument was UMS-100 ultrasonic material characterization system.

[0239] XRD test: The microcrystalline glass sheet is ground into glass fine powder with a grinding machine, and its particle size is less than 75μm, and then it is tested by an X-ray diffractometer (Shimadzu's XRD-6100) to obtain an XRD diffraction peak curve. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6100, the target material is copper, the test incident angle range is 2θ=10-80°, the scanning speed is 0.2° / min, the working voltage is 40kV, and the working current is 30mA. The XRD diffraction data is analyzed by JADE software to obtain the crystal phase of the sample.

[0240] Average grain size: Using the result data obtained from the XRD test, according to the Scherrer formula D = Kλ / (βcosθ), we can calculate the average grain size of the sample, where λ is the X-ray wavelength, λ is 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and Peak FWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, and the Peak FWHM value is converted into radians β = (FWHM / 180*3.14), the grain size of each diffraction peak is calculated by D = Kλ / (βcosθ) and then averaged to obtain the average grain size.

[0241] Testing method for crystal content / crystallinity: Import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud), perform fitting and calculation, and then obtain the crystal content / crystallinity in the microcrystalline glass sample. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content, which is also referred to as crystallinity in the present invention.

[0242] b value determination: The b value was obtained by testing the sample using a Konica Minolta spectrophotometer CM-3600A from Japan, and the average value of 5 parallel samples was taken as the b value result of the sample to be tested.

[0243] Transmittance determination: Test according to GB / T 7962.12-2010 Test Method for Colorless Optical Glass Part 12: Spectral Transmittance. First, clean the glass-ceramic sample in an ultrasonic cleaner. The cleaning conditions are: cleaning time 5-10 minutes; cleaning agent used: commonly used detergent diluted 10 times; cleaning temperature: 45℃-65℃; cleaning frequency: 20KHZ-40KHZ. Then use a haze meter (Japan Konica Minolta spectrophotometer CM-3600A) to test its transmittance under different wavelengths of light.

[0244] The transmittance of the sample under 550nm wavelength light was measured using a Konica Minolta spectrophotometer CM-3600A from Japan, and the average value of 5 parallel samples was taken as the transmittance result of the sample to be tested under 550nm wavelength light.

[0245] Thickness of glass: Determined by micrometer test. It should be understood that in the thickness direction, the degree of ion exchange changes gradually from the surface to the center, and the total Na-K and / or Li-Na exchange amount generally does not exceed 1% of the total mass of the sample, and the difference in ion radius is at the pm level, so the expansion effect in the thickness direction is very slight, and it can be approximately considered that the thickness has basically not changed. That is, the thickness change of microcrystalline glass before and after chemical strengthening is very small and can be ignored.

[0246] Density determination: The density of the glass-ceramic sample is tested according to the principle of the “Archimedes drainage method”. The testing instrument used in the present invention is an ALFA MIRAGE electronic density balance SD-200L.

[0247] After completing the above-mentioned performance tests, the 0.7 mm thick microcrystalline glass sample obtained above is then chemically strengthened according to the mixed or single molten salt composition, ion exchange step temperature and ion exchange time conditions shown in Table 2 to obtain strengthened microcrystalline glass.

[0248] The sample is subjected to single-step strengthening, and the specific process is as follows:

[0249] IOX (ion exchange): 480°C × 100% KNO3 × 24h (refers to exchange in 100wt% KNO3 molten salt at 480°C for 24h; similar expressions in this article have similar meanings, and the molten salt temperature, composition, and ion exchange time used for ion exchange are abbreviated in this form);

[0250] The physical properties of the prepared strengthened glass-ceramics were tested according to the following method:

[0251] In the present invention, CS_50, |CT_CV|, |CT_AV|, and DOL_0 are tested using the stress meter SLP-2000 of Japan Luceo (Japan Orihara), and the test conditions are: light source wavelength is 518nm, SOC=25.5 (nm / cm) / MPa, refractive index=1.60, and exposure time: 300usec. When testing CS_50, |CT_CV|, |CT_AV|, and DOL_0, it is necessary to first drip a special refractive liquid on the stress meter, then wipe the strengthened microcrystalline glass product clean, and place it on the test path to test its stress value. The refractive index of the refractive liquid used for SLP-2000 is 1.51. Unless otherwise specified, the above-mentioned test conditions are used when testing stress values ​​in the embodiments and comparative examples of the present invention. It should be noted that when testing the stress values ​​of comparative examples 8-18, the photoelastic constant was set to 25.5 and the refractive index nd was 1.6; when testing the stress value of comparative example 7, the photoelastic constant was set to 25.5 and the refractive index nd was 1.54; when testing the stress value of comparative example 8, the photoelastic constant was set to 28.6 and the refractive index nd was 1.51.

[0252] The tensile stress line density CT_LD is related to the thickness of the glass sheet, the strengthening depth and the average tensile stress, and can be used to evaluate the drop resistance of the glass sheet. In the present invention, the CT_LD is calculated according to the following formula:

[0253]

[0254] Where t represents the thickness of the glass-ceramic sheet (the glass thickness in the following embodiments and comparative examples of the present invention is 0.7 mm), in mm; DOL_0 represents the depth of the compressive stress layer, in μm; CT_AV represents the internal average tensile stress, and its absolute value is taken in the calculation, in MPa. It should be understood that in the calculation formula of the tensile stress linear density, the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained, and the unit does not participate in the calculation.

[0255] The calculation method of the exchange amount is: the ratio of the mass difference of the microcrystalline glass sheet before and after chemical strengthening to the mass of the microcrystalline glass sheet before chemical strengthening.

[0256] Surface K2O concentration test: In the present invention, the K2O concentration on the surface of the strengthened microcrystalline glass is measured by an X-ray fluorescence spectrometer (XRF). The equipment model used is (Thermo Scientific ARL PERFORM'X), the target material is Rh (rhodium), the light tube voltage is 40kW, the current is 60mA, the collimator is 0.15, the crystal is LiF200, the detector is FPC, the test range is 29mm circle, and the analysis software is UniQuant standardless analysis.

[0257] Vickers hardness (HV) test: The chemically strengthened strengthened microcrystalline glass is made into a small piece with a length, width and thickness of 50mm*50mm*0.7mm, and a glass sample with a clean surface and no visible scratches, pits, cracks and other damage is selected as a test sample, and then the Vickers hardness is measured using a Vickers hardness tester. The Vickers hardness tester used in the present invention is a digital display small load Vickers hardness tester (Beijing Kewei Technology Co., Ltd., VTD405). Test conditions: load 300gf, load time 10s, the effectiveness of the indentation complies with the "GB / T37900-2019 Ultra-thin glass hardness and fracture toughness test method small load Vickers hardness indentation method" standard. Select 3 different positions on the same sample surface for measurement, and select the average value of the 3 measurement results as the Vickers hardness result of the glass sample to be tested.

[0258] Fracture toughness test: Test according to GB / T 37900-2019 Ultra-thin glass hardness and fracture toughness test method Small load Vickers hardness indentation method. Specifically, the indentation is prepared in the same way as the Vickers hardness measurement, and the crack length 2C1, 2C2 in the diagonal direction of the indentation is measured, and its maximum value cannot exceed the thickness of the glass. At least 5 effective indentation morphologies are measured on the surface of one sample, and the average value is calculated as the final result value of the sample.

[0259] Indentation fracture toughness calculation formula:

[0260] IFR: Indentation fracture toughness, unit is MPa·m 1 / 2 ); E: elastic modulus of the specimen, in GPa; 2C1, 2C2: crack extension length in the diagonal direction of the indentation, in millimeter (mm); d1, d2: diagonal length of the indentation, in millimeter (mm); F: test load value, in Newton (N).

[0261] Test method for average drop resistance height: The average sandpaper drop resistance height refers to the average value of the sandpaper drop resistance height of each sample measured in multiple identical glass samples, which can be used to characterize the drop resistance performance of microcrystalline glass. At least 10 identical glass samples are tested in each batch, and the average sandpaper drop resistance height is:

[0262]

[0263] Where n is the number of glass samples tested in each batch, hi is the sandpaper drop resistance height of a single sample test;

[0264] Among them, the test method for the sandpaper drop height of a single sample is:

[0265] Step 1: Paste 120-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;

[0266] Step 2: Place a glass sample to be tested with a length, width and thickness of 50mm*50mm*0.7mm directly under the model machine, with the glass sample facing the sandpaper. Make the model machine fall from a certain drop height to impact the glass sample directly under the model machine. If the glass sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, increase the height by 0.1m each time and drop again until the glass sample breaks;

[0267] Step 3: The last drop height of the glass sample when it breaks is recorded as the anti-sandpaper drop height. For example, if the drop height when it breaks is 0.5m, the anti-sandpaper drop height of the sample is 0.4m.

[0268] Test method for 2.5m drop test pass rate: 2.5m drop test pass rate refers to the number of samples that pass after a drop test from a height of 2.5m divided by the total number of test samples. The percentage of passed samples is calculated. After the drop test, if the glass sample does not break, it is recorded as passed, otherwise it is recorded as failed. It can be used to characterize the drop resistance of microcrystalline glass. Take at least 10 identical microcrystalline glass samples for each batch for testing.

[0269] Specifically, the method for a single sample to undergo a 2.5m drop test is as follows:

[0270] Step 1: Paste 120-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;

[0271] Step 2: Place a glass sample with a length, width and thickness of 50mm*50mm*0.7mm directly under the model machine, with the glass sample facing the sandpaper. Make the model machine fall once from a drop height of 2.5m to impact the glass sample directly under the model machine. If the glass sample does not break, it is recorded as passed, otherwise it is recorded as failed.

[0272] Test method for high temperature and high humidity failure time: Use QTH_80C full temperature and humidity alternating test chamber for testing, and the alternating test chamber conditions are set as follows: temperature is 85°C and relative humidity is 85%. Take out the sample every 12 hours, and wipe the glass surface with a dust-free cloth to observe whether there are spots or fog spots that cannot be wiped off. If the sample has spots or fog spots that cannot be wiped off during this observation, and the last time it was taken out for observation, the sample did not have spots or fog spots that cannot be wiped off, then the time the glass sample was taken out for this observation is used as the node, and the time the glass sample was placed in the test chamber is calculated, which is recorded as the high temperature and high humidity failure time of the test sample, which is used to characterize weather resistance.

[0273] Examples 2-6 were operated under the same operating conditions as Example 1, and corresponding tests were performed. Table 1 shows the glass formula compositions and heat treatment processes for preparing the substrate glass and the performance parameters of the chemically strengthened glass-ceramics obtained. Table 2 shows the strengthening conditions of the chemically strengthened glass-ceramics in Examples 1-5 and the performance parameters of the prepared strengthened glass-ceramics. The chemically strengthened glass-ceramics used in Example 6 is the same as that in Example 1.

[0274] Table 1 Base glass formula, melting state, heat treatment process and performance parameters of chemically strengthened microcrystalline glass prepared in Examples 1-5

[0275]

[0276]

[0277]

[0278] Table 2 Chemical strengthening conditions of the chemically strengthened glass-ceramics in Examples 1-6 and performance parameters of the prepared strengthened glass-ceramics

[0279]

[0280]

[0281] Note: 1. Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours; 2. The surface K2O content in the table is the surface K2O concentration in the present invention.

[0282] Examples 7-13 respectively use the same chemically strengthened glass-ceramics as Examples 1, 2, 3, and 4, and operate under different strengthening conditions. The specific strengthening conditions used and the performance parameters of the prepared strengthened glass-ceramics are shown in Table 3.

[0283] Table 3 Chemical strengthening conditions of Examples 7-13 and performance parameters of the strengthened microcrystalline glass prepared therefrom

[0284]

[0285]

[0286] Note: 1. Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours; 2. The surface K2O content in the table is the surface K2O concentration in the present invention.

[0287] Figure 1 The thermogravimetric analysis curve of the substrate glass of Example 1, wherein the thermogravimetric analysis test method is as follows: grind the substrate glass of Formula 1 of Example 1 and pass it through a 200-mesh sieve; the test conditions are: room temperature to 1100°C, 10°C / min heating rate; the test instrument is Mettler-Toledo TGA / DSC3+ thermogravimetric and synchronous thermal analyzer. The obtained raw data is imported into OriginPro software to obtain Figure 1 The thermogravimetric analysis curve shown below shows the endothermic peak. Figure 1 It can be seen that the first endothermic peak is 735°C; upward is the exothermic peak, and the first exothermic peak is 848°C.

[0288] Figure 2 is the XRD diffraction pattern of the chemically strengthened spinel glass-ceramics of Example 1, Figure 2 It can be seen that the main crystalline phase of the microcrystalline glass is (Zn, Mg)Al2O4 (card numbers: 74-1136 and 73-1959), and the secondary crystalline phase is zirconium oxide (card number: 80-1007).

[0289] Figure 3 is the transmittance curve of the chemically strengthened glass-ceramics of Example 1 under different wavelength conditions, Figure 3 It can be seen that the transmittance of the microcrystalline glass at a wavelength of 550nm is greater than 90%.

[0290] Figure 4 This is a diagram showing the melting results of the substrate glass of Example 1. Figure 5 This is a diagram showing the melting results of the substrate glass of Example 3. Figure 6 The appearance of the chemically strengthened glass-ceramics of Example 3 is shown in FIG. Figure 4-6 It can be seen that the base glass prepared by the glass formula of the present invention and the microcrystalline glass prepared by a specific heat treatment process are both transparent glass materials in the visible light range.

[0291] As can be seen from Tables 1-3, the chemically strengthened glass-ceramics prepared by the glass formula provided by the present invention is a glass-ceramics with a main crystal phase of (Zn, Mg)Al2O4, a secondary crystal phase of zirconium oxide, a high degree of crystallinity and excellent optical properties. Specifically, the crystallinity of the chemically strengthened glass-ceramics of the present invention is 37.52-40.41%, and the Young's modulus is above 101GPa. The transmittance of the chemically strengthened glass-ceramics of the present invention at a wavelength of 550nm is greater than or equal to 89%. The strengthened microcrystalline glass of the present invention has both excellent surface stress characteristics and excellent deep stress characteristics. Specifically, the CS_50 of the strengthened microcrystalline glass of the present invention is 148.02-317.95MPa, |CT_CV| is 89.07-145.86MPa, |CT_AV| is 77.90-121.45MPa, and DOL_0 is 108.69-138.96μm, all of which are greater than 0.13 times the glass thickness (0.7mm). The CT_LD is 52482-80192MPa / mm, and the calculated result of exp((|CT-CV|-|CT_AV|) / (t / 2-DOL_0)*2) is 1.08-1.24, all of which are less than 1.30, and the fracture toughness is 1.51-1.66MPa·m 1 / 2 , high fracture toughness can improve the damage resistance and / or drop performance of strengthened microcrystalline glass; higher |CT_AV|, |CT_CV|, DOL_0, CT_LD and CS_50 indicate that strengthened microcrystalline glass has excellent deep stress. The surface K2O content (that is, surface K2O concentration) is 9.16-15.21%. It should be understood that the K on the surface of strengthened microcrystalline glass mainly enters the glass surface through the chemical strengthening process and salt bath exchange. The higher the surface K2O content, the more K-Na exchange occurs during the strengthening process, and the higher the surface compressive stress that the microcrystalline glass can obtain, and the better the surface stress characteristics. The anti-drop test results show that the average sandpaper drop height (120 mesh sandpaper) of the strengthened microcrystalline glass of the present invention can reach more than 2.0m. At the same time, when dropped from a fixed height of 2.5m, the pass rate of the strengthened microcrystalline glass of the present invention is more than 70%.

[0292] In addition, the high temperature and high humidity failure time of the strengthened microcrystalline glass of the present invention can reach more than 360 hours, indicating that the strengthened microcrystalline glass of the present invention has excellent weather resistance.

[0293] In the drop test of the strengthened sample (i.e., strengthened microcrystalline glass) in the embodiment of the present invention, the proportion of fragments with a maximum vertical projection size greater than 5 mm in the entire glass is 83.27-99.77%, and the average maximum size of fragments with a maximum vertical projection size greater than 1 mm is 6.47-51.15 mm.

[0294] Comparative Examples 1-6 were operated and tested under the same operating conditions as Example 1. Table 4 shows the glass formula compositions of the substrate glasses prepared in Comparative Examples 1-6 and the melting states of the prepared substrate glasses.

[0295] Table 4 Glass formula composition of the prepared substrate glass in Comparative Examples 1-6 and the melting state of the prepared substrate glass

[0296]

[0297] It can be seen from Table 4 that the B value in Comparative Example 1 is 0.89, which is greater than 0.8. Figure 7 As shown, the substrate glass is ceramicized after melting; in Comparative Example 2, the Al2O3 content is too high, the B2O3 content is low and the A value is 0.24, which is greater than 0.18, resulting in melting defects, such as Figure 8 As shown, a large amount of unmelted material appears in the substrate glass after melting; in Comparative Example 3, the B2O3 content is relatively low and the A value is 0.21, which is greater than 0.18. Fig. 9 As shown, white precipitate appears on the substrate glass after melting; in Comparative Example 4, the ZrO2 content is too high and the A value is 0.19, which is greater than 0.18, and white precipitate appears on the substrate glass after melting; in Comparative Example 5, the MgO content is relatively high and the B value is 0.84, which is greater than 0.8, and the substrate glass is ceramicized after melting; in Comparative Example 6, the ZnO content is relatively high and the B value is 1.05, which is greater than 0.8, and the melting condition is as follows Fig.10 As shown, the base glass becomes ceramic after melting.

[0298] Comparative Examples 7-12 were operated under the same operating conditions as Example 1 and were tested accordingly. Table 5 shows the glass formula composition, melting state, heat treatment process and performance parameters of the chemically strengthened glass-ceramics prepared in Comparative Examples 7-12; Table 6 shows the chemical strengthening conditions of the chemically strengthened glass-ceramics prepared in Comparative Examples 7-12 and the performance parameters of the strengthened glass-ceramics prepared therefrom. Among them, Comparative Example 8 did not undergo nucleation and crystallization treatment; Comparative Example 9 did not undergo nucleation treatment, but only underwent one-step heat treatment, i.e., direct temperature increase for crystallization treatment; the inventors also used a heat treatment process different from that of Comparative Example 9 according to the conditions of Comparative Example 9, and performed heat treatment at 800°C for 240 minutes (not shown in Table 5). The inventors found that under this heat treatment condition, the substrate glass corresponding to the glass formula of Comparative Example 9 did not precipitate crystals, but phase separation occurred, and the transmittance decreased; Comparative Example 12 did not undergo nucleation treatment; Comparative Example 9 did not undergo ion strengthening treatment; Comparative Example 7 was strengthened using two conditions, 450°C×100%NaNO3×9h and 450°C×30%NaNO3+70%KNO3×8h.

[0299] Table 5 Glass formula composition, melting state, heat treatment process and performance parameters of chemically strengthened microcrystalline glass prepared in Comparative Examples 7-12

[0300]

[0301]

[0302]

[0303] Table 6 Chemical strengthening conditions of chemically strengthened glass-ceramics prepared in Comparative Examples 7-12 and performance parameters of the strengthened glass-ceramics prepared therefrom

[0304]

[0305]

[0306] Note: 1. Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours; 2. The surface K2O content in the table is the surface K2O concentration in the present invention.

[0307] It should be noted that the glass formula of Comparative Example 8 contains K2O, so the measured surface K2O is not entirely the result of ion exchange. Therefore, the surface K2O value of Comparative Example 8 is not given in Table 6.

[0308] Comparative Examples 13-18 were operated under the same operating conditions as Example 1, and corresponding tests were performed. Table 7 shows the glass formula composition, melting state, heat treatment process, and performance parameters of the chemically strengthened glass-ceramics prepared in Comparative Examples 13-18; Table 8 shows the chemical strengthening conditions of the chemically strengthened glass-ceramics prepared in Comparative Examples 13-15 and the performance parameters of the strengthened glass-ceramics prepared therefrom; In addition, Comparative Examples 16-18 were not subjected to strengthening treatment.

[0309] Table 7 Glass formula composition, melting state, heat treatment process and performance parameters of chemically strengthened microcrystalline glass prepared by comparative examples 13-18

[0310]

[0311]

[0312] Table 8 Chemical strengthening conditions of chemically strengthened glass-ceramics prepared in Comparative Examples 13-15 and performance parameters of the strengthened glass-ceramics prepared therefrom

[0313]

[0314] Note: 1. Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours; 2. The surface K2O content in the table is the surface K2O concentration in the present invention.

[0315] It can be seen from Tables 5 and 7 that in Comparative Example 9, the Na2O content is low. When the heat treatment temperature is lower than 800°C, no crystalline phase appears in the glass after heat treatment. When the heat treatment temperature reaches 900°C, mullite impurity phase appears after crystallization treatment. The transmittance of the finally obtained microcrystalline glass sample is low, showing devitrification; in Comparative Example 16, the MgO content is low, the average grain size of the microcrystalline glass sample after crystallization is too large, the transmittance is low, and the optical properties of the sample are poor; in Comparative Example 17, the ZnO content is low, the average grain size of the microcrystalline glass sample after crystallization is too large and impurity phase appears, the transmittance is low, and the optical properties of the sample are poor; in Comparative Example 18, the Li2O content is high, the microcrystalline glass sample after crystallization is severely fogged as a whole, the average grain size is too large, and impurity phase quartz SS appears, the transmittance is low, and the optical properties of the sample are extremely poor. Fig.11 shown.

[0316] It can be seen from Tables 6 and 8 that the Al2O3 content in Comparative Example 10 is low, and the stress level of the finally prepared strengthened microcrystalline glass is low, and the drop impact resistance is poor; the X value in Comparative Example 12 is 23.94%, and the Y value is 44.77%, and the X value in Comparative Example 13 is 29.95%, and the Y value is 55.08%, all of which do not meet the conditions of X=30-50% and Y=60-80%. Finally, the stress level of the strengthened microcrystalline glass prepared by the two is also poor. Specifically, when the drop test is carried out using 120-mesh sandpaper, the average anti-sandpaper drop height of the strengthened microcrystalline glass in Comparative Examples 12 and 13 is less than 1.4m, which is much lower than the strengthened microcrystalline glass prepared in the embodiment of the present invention. At the same time, the strengthened microcrystalline glass in Comparative Examples 12 and 13 is tested at a fixed point of 2.5m. During the height drop test, the glass was broken and the pass rate was 0; the Y value in Comparative Example 14 did not meet the condition of 60-80%, and the component contained BaO, and the Al2O3 content did not meet the requirements of the present invention. Finally, the stress level of the strengthened microcrystalline glass obtained in Comparative Example 14 was poor. When the drop test was performed using 120-mesh sandpaper, the average sandpaper drop height was 0.6m, which was much lower than the strengthened microcrystalline glass obtained in the embodiment of the present invention. At the same time, when the 2.5m fixed-point height drop test was performed, the test pass rate of the strengthened microcrystalline glass in Comparative Example 14 was also 0; the X value of Comparative Example 11 was 38.15% and the Y value was 66.64%, but the component contained 2.21mol% BaO, and the stress level obtained after the final strengthening was low, and the drop impact resistance was poor. The X value of Comparative Example 15 is 35.50% and the Y value is 59.10%. The X value meets the condition of 30-50%, and the Y value does not meet the condition of 60-80%. The deep stress level of the obtained strengthened microcrystalline glass is poor. When the drop test is carried out using 120-mesh sandpaper, the average sandpaper resistance drop height is 1.02m, which is much lower than the strengthened microcrystalline glass obtained in the embodiment of the present invention.

[0317] For Comparative Example 7, when the high-crystallinity lithium aluminum silicon strengthened microcrystalline glass is dropped with 120-mesh sandpaper for a drop test, the average sandpaper drop height is 1.98m-2.14m, and when the 2.5m fixed-point height drop test is carried out, the pass rate is 60-70%, the fracture toughness is 1.310-1.391, and the high temperature and high humidity failure time is 72-168h; for Comparative Example 8, when the existing ordinary two-step strengthened glass is dropped with 120-mesh sandpaper for a drop test, the average sandpaper drop height is 1.25m, and when the 2.5m fixed-point height drop test is carried out, the pass rate is 0, and the fracture toughness is 1.322.

[0318] Comparative Examples 19-24 were operated and tested according to the same strengthening conditions as Example 1. Table 9 shows the chemical strengthening conditions used in Comparative Examples 19-24 and the performance parameters of the strengthened glass-ceramics prepared therefrom.

[0319] Table 9 Chemical strengthening conditions of comparative examples 19-24 and performance parameters of the strengthened microcrystalline glass prepared therefrom

[0320]

[0321]

[0322] Note: 1. Since the maximum time for high temperature and high humidity failure test in the present invention is 360h (15 days), if the glass sample is taken out for observation after 360h, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360h; 2. The surface K2O content in the table is also the surface K2O concentration in the present invention; 3. Since the upper limit of the test height of the drop machine used for the drop test is 2.5m, if the glass is still not broken after the drop test reaches the upper limit test height, it is judged that the average sandpaper drop height of the glass is greater than 2.5m.

[0323] It can be seen from Table 9 that comparative examples 19-24 were not strengthened according to the stress distribution requirements of the present invention, and the results calculated by exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2) were 1.30-1.96. In the drop test of the strengthened microcrystalline glass samples after strengthening, the fragments with the maximum vertical projection size greater than 5 mm accounted for 0-10.31% of the overall glass. Although the samples after strengthening have excellent drop impact resistance, the fragments are too small after falling and are very easy to splash, which does not meet the fragment safety requirements and the requirements of the safe stress state.

[0324] Depend on Figure 12-15 It can be seen that the size of the fragments of the strengthened micro-ceramics of the present invention after falling is significantly larger than that of the comparative example. Fig.16 It can be seen that after falling, the tempered glass of Example 2 has significantly more fragments with a maximum size greater than 1 mm than that of Comparative Example 20, and the maximum average size is much larger than that of Comparative Example 20. Therefore, the tempered glass of the present invention has excellent safety performance.

[0325] In summary, the strengthened microcrystalline glass of the present invention has excellent mechanical properties, such as excellent drop impact resistance, that is, excellent drop resistance. Specifically, the average sandpaper drop resistance height of the strengthened microcrystalline glass of the present invention (tested with 120-mesh sandpaper) is as high as 2m or more. At the same time, when conducting a fixed-point height drop test of 2.5m, the pass rate of the strengthened microcrystalline glass of the present invention is greater than or equal to 70%. The drop level is equivalent to that of the high-crystallinity lithium aluminum silicon microcrystalline strengthened glass in Comparative Example 7, and is much higher than the existing ordinary two-step strengthened glass in Comparative Example 8.

[0326] At the same time, the embodiments of the present invention all satisfy the formula exp((|CT_CV|-|CT_AV|) / (t / 2-DOL_0)*2)<1.30. The strengthened microcrystalline glass samples have excellent anti-drop performance and the fragments after breaking are not too small. The drop breakage test results show that the proportion of fragments with a maximum vertical projection size greater than 5mm accounts for >80% of the total glass, and the average maximum size of fragments with a maximum vertical projection size greater than 1mm is greater than 5mm, which has excellent safety performance.

[0327] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A drop-resistant tempered glass-ceramic with a safe stress state, the tempered glass-ceramic comprising a compressive stress layer and a tensile stress layer, characterized in that: The strengthened microcrystalline glass contains spinel crystals, and the spinel crystals are the main crystalline phase of the strengthened microcrystalline glass; the composition of the strengthened microcrystalline glass substantially does not contain Li2O, and the Li2O content is less than 0.01% in mol%; The strengthened glass-ceramics meets the following conditions: CS_50≥100MPa, ∣CT_AV∣≥70MPa, DOL_0≥0.13t; exp((∣CT_CV∣-∣CT_AV∣) / (t / 2-DOL_0)*2)<1.30; Where, t is the thickness of the glass-ceramic in μm, DOL_0 is in μm, CS_50, The unit of |CT_CV| and |CT_AV| is MPa; Wherein, CS_50 refers to the compressive stress value at a depth of 50 μm from the glass surface; The |CT_CV| refers to the absolute value of the maximum value of tensile stress; The |CT_AV| refers to the absolute value of the average tensile stress; The DOL_0 refers to the depth of the compressive stress layer.

2. The tempered glass-ceramics according to claim 1, characterized in that: A drop and breakage test was performed on the tempered microcrystalline glass. Among the fragments generated when the tempered microcrystalline glass was dropped and broken, the fragments whose longest side of the vertical projection on the two-dimensional drawing was greater than 5 mm accounted for more than 70% of the total weight of the glass.

3. The tempered glass-ceramics according to claim 1, characterized in that: A drop and breakage test was performed on the tempered microcrystalline glass. Among the fragments generated when the tempered microcrystalline glass fell and broke, the fragments whose longest side of the vertical projection on the two-dimensional drawing was greater than 5 mm accounted for more than 80% of the total weight of the glass.

4. The tempered glass-ceramics according to claim 1, characterized in that: 500MPa≥CS_50≥140MPa; and / or, 200MPa≥|CT_AV|≥70MPa; And / or, 0.22t≥DOL_0≥0.15t.

5. The tempered glass-ceramics according to claim 2, characterized in that: 500MPa≥CS_50≥140MPa; and / or, 200MPa≥|CT_AV|≥70MPa; And / or, 0.22t≥DOL_0≥0.15t.

6. The tempered glass-ceramics according to claim 1, characterized in that: The |CT_CV| of the strengthened glass-ceramics is ≥80MPa, and the unit of |CT_CV| is MPa.

7. The tempered glass-ceramics according to claim 2, characterized in that: The |CT_CV| of the strengthened glass-ceramics is ≥80MPa, and the unit of |CT_CV| is MPa.

8. The tempered glass-ceramics according to claim 4, characterized in that: The |CT_CV| of the strengthened glass-ceramics is ≥80MPa, and the unit of |CT_CV| is MPa.

9. The tempered glass-ceramics according to claim 1, characterized in that: In the tempered glass-ceramics: 300MPa≥|CT_CV|≥80MPa, and the unit of |CT_CV| is MPa.

10. The tempered glass-ceramics according to claim 1, characterized in that: The surface K2O concentration of the strengthened microcrystalline glass is ≥9.00wt%.

11. The tempered glass-ceramics according to claim 2, characterized in that: The surface K2O concentration of the strengthened microcrystalline glass is ≥9.00wt%.

12. The tempered glass-ceramics according to claim 4, characterized in that: The surface K2O concentration of the strengthened microcrystalline glass is ≥9.00wt%.

13. The tempered glass-ceramics according to claim 6, characterized in that: The surface K2O concentration of the strengthened microcrystalline glass is ≥9.00wt%.

14. The tempered glass-ceramics according to claim 1, characterized in that: The surface K2O concentration of the strengthened glass-ceramics is 9.00-16.00 wt%.

15. The tempered glass-ceramics according to claim 1, characterized in that: The CT_LD of the strengthened glass-ceramics is 40000MPa / mm-85000MPa / mm, where CT_LD refers to the tensile stress linear density.

16. The tempered glass-ceramics according to claim 2, characterized in that: The CT_LD of the strengthened glass-ceramics is 40000MPa / mm-85000MPa / mm, where CT_LD refers to the tensile stress linear density.

17. The strengthened glass-ceramics according to claim 4, characterized in that: The CT_LD of the strengthened glass-ceramics is 40000MPa / mm-85000MPa / mm, where CT_LD refers to the tensile stress linear density.

18. The tempered glass-ceramics according to claim 6, characterized in that: The CT_LD of the strengthened glass-ceramics is 40000MPa / mm-85000MPa / mm, where CT_LD refers to the tensile stress linear density.

19. The tempered glass-ceramics according to claim 10, characterized in that: The CT_LD of the strengthened glass-ceramics is 40000MPa / mm-85000MPa / mm, where CT_LD refers to the tensile stress linear density.

20. The strengthened glass-ceramics according to claim 1, characterized in that: The CT_LD of the strengthened glass-ceramics is 45000MPa / mm-85000MPa / mm, where CT_LD refers to the tensile stress linear density.

21. The strengthened glass-ceramics according to claim 1, characterized in that: The CT_LD of the strengthened glass-ceramics is 48000MPa / mm-85000MPa / mm, where CT_LD refers to the tensile stress linear density.

22. The strengthened glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

23. The strengthened glass-ceramics according to claim 2, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

24. The strengthened glass-ceramics according to claim 4, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

25. The strengthened glass-ceramics according to claim 6, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

26. The strengthened glass-ceramics according to claim 10, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

27. The strengthened glass-ceramics according to claim 15, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

28. The strengthened glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is 20.00 to 50.00 wt %.

29. The strengthened glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is 30.00 to 50.00 wt %.

30. The strengthened glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is 35.00-45.00 wt %.

31. The strengthened glass-ceramics according to claim 1, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

32. The strengthened glass-ceramics according to claim 2, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

33. The strengthened glass-ceramics according to claim 4, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

34. The strengthened glass-ceramics according to claim 6, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

35. The strengthened glass-ceramics according to claim 10, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

36. The strengthened glass-ceramics according to claim 15, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

37. The strengthened glass-ceramics according to claim 22, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

38. The strengthened glass-ceramics according to claim 31, characterized in that: In the strengthened glass-ceramics, an average grain size is 1.0 to 15.0 nm.

39. The strengthened glass-ceramics according to claim 31, characterized in that: In the strengthened microcrystalline glass, the average grain size is 1 to 10 nm.

40. The strengthened glass-ceramics according to claim 31, characterized in that: In the strengthened microcrystalline glass, the average grain size is 4.5 to 8.0 nm.

41. The strengthened glass-ceramics according to claim 1, characterized in that: In terms of mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50~30.00%, ZrO23.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na2O7.20~14.00%, B2O33.00~8.00%, K2O 0~2.00% and Y2O30~1.00%.

42. The strengthened glass-ceramics according to claim 2, characterized in that: In terms of mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50~30.00%, ZrO23.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na2O7.20~14.00%, B2O33.00~8.00%, K2O 0~2.00% and Y2O30~1.00%.

43. The strengthened glass-ceramics according to claim 4, characterized in that: In terms of mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50~30.00%, ZrO23.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na2O7.20~14.00%, B2O33.00~8.00%, K2O 0~2.00% and Y2O30~1.00%.

44. The strengthened glass-ceramics according to claim 6, characterized in that: In terms of mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50~30.00%, ZrO23.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na2O7.20~14.00%, B2O33.00~8.00%, K2O 0~2.00% and Y2O30~1.00%.

45. The strengthened glass-ceramics according to claim 10, characterized in that: Calculated in mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%.

46. ​​The strengthened glass-ceramics according to claim 15, characterized in that: Calculated in mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%.

47. The strengthened glass-ceramics according to claim 22, characterized in that: Calculated in mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%.

48. The strengthened glass-ceramics according to claim 31, characterized in that: Calculated in mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%.

49. The strengthened glass-ceramic according to any one of claims 41 to 48, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.

18. (1)A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3; and / or, The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.

80. (2)B=3.8×Na2O+B2O3+4.5×MgO+6.0×ZnO-0.4×Al2O3-SiO2.

50. The strengthened glass-ceramics according to claim 49, characterized in that: The A value is 0.05 to 0.15; And / or, the B value is 0.60 to 0.

78.

51. The strengthened glass-ceramic according to any one of claims 41 to 48, characterized in that: In the tensile stress layer of the strengthened glass-ceramics, the molar percentage of SiO2 is 38.00-44.00%; And / or, the molar percentage of Na2O is 7.20-13.00%; And / or, the molar percentage of Al2O3 is 25.50-28.00%; And / or, the molar percentage of MgO is 5.00-7.00%; And / or, the molar percentage of ZnO is 8.00-12.00%; And / or, the molar percentage of B2O3 is 3.00-7.00%.

52. The strengthened glass-ceramics according to claim 49, characterized in that: In the tensile stress layer of the strengthened glass-ceramics, the molar percentage of SiO2 is 38.00-44.00%; And / or, the molar percentage of Na2O is 7.20-13.00%; And / or, the molar percentage of Al2O3 is 25.50-28.00%; And / or, the molar percentage of MgO is 5.00-7.00%; And / or, the molar percentage of ZnO is 8.00-12.00%; And / or, the molar percentage of B2O3 is 3.00-7.00%.

53. The strengthened glass-ceramics according to claim 51, characterized in that: In the tensile stress layer of the strengthened glass-ceramics, the molar percentage of Na2O is 7.20-12.00%; And / or, the molar percentage of MgO is 5.00-6.50%; And / or, the molar percentage of ZnO is 8.00-10.50%; And / or, the molar percentage of B2O3 is 3.00-6.50%.

54. The strengthened glass-ceramics according to any one of claims 41 to 48, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

55. The strengthened glass-ceramics according to claim 49, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

56. The strengthened glass-ceramics according to claim 51, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

57. The strengthened glass-ceramic according to any one of claims 41 to 48, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed as a molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

58. The strengthened glass-ceramics according to claim 49, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (5)Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

59. The strengthened glass-ceramics according to claim 51, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (6) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

60. The strengthened glass-ceramics according to claim 54, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (7) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

61. The strengthened glass-ceramics according to claim 57, characterized in that: The value of X is calculated, and the value of X is 34.00% to 46.00%, and / or the value of Y is calculated, and the value of Y is 60.00% to 75.00%.

62. The strengthened glass-ceramic according to any one of claims 41 to 48, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: does not contain BaO, and the BaO content is less than 0.01% by mol%; And / or does not contain TiO2, and the TiO2 content is less than 0.01% by mol%.

63. The strengthened glass-ceramics according to claim 49, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: does not contain BaO, and the BaO content is less than 0.01% by mol%; And / or does not contain TiO2, and the TiO2 content is less than 0.01% by mol%.

64. The strengthened glass-ceramics according to claim 51, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: does not contain BaO, and the BaO content is less than 0.01% by mol%; And / or does not contain TiO2, and the TiO2 content is less than 0.01% by mol%.

65. The strengthened glass-ceramics according to claim 54, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: does not contain BaO, and the BaO content is less than 0.01% by mol%; And / or does not contain TiO2, and the TiO2 content is less than 0.01% by mol%.

66. The strengthened glass-ceramics according to claim 57, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: does not contain BaO, and the BaO content is less than 0.01% by mol%; And / or does not contain TiO2, and the TiO2 content is less than 0.01% by mol%.

67. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

68. The strengthened glass-ceramics according to claim 49, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

69. The strengthened glass-ceramics according to claim 51, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

70. The strengthened glass-ceramics according to claim 54, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

71. The strengthened glass-ceramics according to claim 57, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

72. The strengthened glass-ceramics according to claim 62, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

73. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

74. The strengthened glass-ceramics according to claim 49, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

75. The strengthened glass-ceramics according to claim 51, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

76. The strengthened glass-ceramics according to claim 54, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

77. The strengthened glass-ceramics according to claim 57, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

78. The strengthened glass-ceramics according to claim 62, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

79. The strengthened glass-ceramics according to claim 67, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

80. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

81. The strengthened glass-ceramics according to claim 49, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

82. The strengthened glass-ceramics according to claim 51, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

83. The strengthened glass-ceramics according to claim 54, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

84. The strengthened glass-ceramics according to claim 57, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

85. The strengthened glass-ceramics according to claim 62, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

86. The strengthened glass-ceramics according to claim 67, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

87. The strengthened glass-ceramics according to claim 73, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

88. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.20 MPa·m 1 / 2 .

89. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.50 MPa·m 1 / 2 .

90. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

91. The strengthened glass-ceramics according to claim 49, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

92. The strengthened glass-ceramics according to claim 51, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

93. The strengthened glass-ceramics according to claim 54, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

94. The strengthened glass-ceramics according to claim 57, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

95. The strengthened glass-ceramics according to claim 62, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

96. The strengthened glass-ceramics according to claim 67, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

97. The strengthened glass-ceramics according to claim 73, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

98. The strengthened glass-ceramics according to claim 80, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

99. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than or equal to 1.80 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

100. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass was subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass was 1.80 to 2.50 m; the average sandpaper drop resistance height was based on tests of at least 10 samples.

101. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass was subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass was 2.00 to 2.50 m; the average sandpaper drop resistance height was based on tests of at least 10 samples.

102. The strengthened glass-ceramics according to any one of claims 1 to 48, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

103. The strengthened glass-ceramics according to claim 49, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

104. The strengthened glass-ceramics according to claim 51, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

105. The strengthened glass-ceramics according to claim 54, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

106. The strengthened glass-ceramics according to claim 57, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

107. The strengthened glass-ceramics according to claim 62, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

108. The strengthened glass-ceramics according to claim 67, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

109. The strengthened glass-ceramics according to claim 73, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

110. The strengthened glass-ceramics according to claim 80, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

111. The strengthened glass-ceramics according to claim 90, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

112. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥ 60%; the pass rate is based on the testing of at least 10 samples.

113. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥ 70%; the pass rate is based on the testing of at least 10 samples.

114. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

115. The strengthened glass-ceramics according to claim 49, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

116. The strengthened glass-ceramics according to claim 51, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

117. The strengthened glass-ceramics according to claim 54, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

118. The strengthened glass-ceramics according to claim 57, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

119. The strengthened glass-ceramics according to claim 62, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

120. The strengthened glass-ceramics according to claim 67, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

121. The strengthened glass-ceramics according to claim 73, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

122. The strengthened glass-ceramics according to claim 80, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

123. The strengthened glass-ceramics according to claim 90, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

124. The strengthened glass-ceramics according to claim 102, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

125. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥110 GPa.

126. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: The Young's modulus of the strengthened microcrystalline glass is 114 GPa≤Young's modulus≤140 GPa.

127. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

128. The strengthened glass-ceramics according to claim 49, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

129. The strengthened glass-ceramics according to claim 51, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

130. The strengthened glass-ceramics according to claim 54, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

131. The strengthened glass-ceramics according to claim 57, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

132. The strengthened glass-ceramics according to claim 62, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

133. The strengthened glass-ceramics according to claim 67, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

134. The strengthened glass-ceramics according to claim 73, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

135. The strengthened glass-ceramics according to claim 80, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

136. The strengthened glass-ceramics according to claim 90, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

137. The strengthened glass-ceramics according to claim 102, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

138. The strengthened glass-ceramics according to claim 114, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥240h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

139. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered glass-ceramics is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥300h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered glass-ceramics under the corresponding high temperature and high humidity conditions.

140. The strengthened glass-ceramic according to any one of claims 1 to 48, characterized in that: Under the conditions of 85°C and 85% relative humidity, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥360h. The high temperature and high humidity failure time is the time when spots or fog spots that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.

141. The method for preparing the strengthened glass-ceramics according to any one of claims 1 to 140, characterized in that: The method comprises the following steps: (I) preparing chemically strengthened glass-ceramics: the chemically strengthened glass-ceramics are prepared by heat treating a substrate glass; (II) preparing strengthened glass-ceramics: the chemically strengthened glass-ceramics obtained in step (I) are subjected to chemical strengthening treatment to obtain strengthened glass-ceramics as claimed in any one of claims 1 to 140; The strengthened microcrystalline glass contains spinel crystals, and the spinel crystals are the main crystalline phase of the strengthened microcrystalline glass; the composition of the strengthened microcrystalline glass substantially does not contain Li2O, and the Li2O content is less than 0.01% in mol%; The strengthened glass-ceramics meets the following conditions: CS_50≥100MPa, ∣CT_AV∣≥70MPa, DOL_0≥0.13t; exp((∣CT_CV∣-∣CT_AV∣) / (t / 2-DOL_0)*2)<1.30; Wherein, t is the thickness of the glass-ceramic, in μm.

142. The preparation method according to claim 141, characterized in that The chemical strengthening treatment includes a single-step strengthening method or a multi-step strengthening method.

143. The preparation method according to claim 141, characterized in that The chemical strengthening treatment salt bath is a molten salt containing a potassium salt.

144. The preparation method according to claim 143, characterized in that In the salt bath for chemical strengthening treatment, the concentration of potassium salt is 60wt% to 100wt%.

145. The preparation method according to claim 143, characterized in that The temperature of the chemical strengthening treatment salt bath is 380°C to 600°C.

146. The preparation method according to claim 143, characterized in that The temperature of the chemical strengthening treatment salt bath is 400°C to 550°C.

147. A chemically strengthened glass-ceramic for preparing the strengthened glass-ceramic according to any one of claims 1 to 40, characterized in that: The chemically strengthened glass-ceramics contain spinel crystals, and the spinel crystals are the main crystalline phase of the glass-ceramics; the composition of the chemically strengthened glass-ceramics contains the following oxides in mol%: SiO238.00-48.00%, Al2O325.50-30.00%, ZrO23.00-5.00%, MgO 5.00-7.50%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O33.00-8.00%, K2O 0-2.00% and Y2O30-1.00%; wherein the chemically strengthened glass-ceramics substantially does not contain Li2O, and Li2O is less than 0.01% in mol%; The composition of the chemically strengthened glass-ceramics, expressed in terms of the content expressed in molar percentage of oxides, satisfies: X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3), wherein X=30.00-50.00%; Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3), where Y=60.00~80.00%.

148. The chemically strengthened glass-ceramics according to claim 147, characterized in that The composition of the chemically strengthened glass-ceramics satisfies the following requirements, expressed in terms of the content expressed as a molar percentage of oxides: A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3, where A≤0.18; and / or, B = 3.8 × Na2O + B2O3 + 4.5 × MgO + 6.0 × ZnO - 0.4 × Al2O3 - SiO2, wherein B ≤ 0.80; and / or, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3), wherein X=34.00-46.00%; and / or, Y = (2.7 × Na2O + 1.8 × (Al2O3-MgO-ZnO)) / (SiO2 + Al2O3-MgO-ZnO + Na2O + K2O + B2O3), wherein Y = 60.00-75.00%; And / or, in the chemically strengthened glass-ceramics, the molar percentages of the components Al2O3, MgO, and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

149. The chemically strengthened glass-ceramics according to claim 148, characterized in that The value of A is 0.05 to 0.15; And / or, the value of B is 0.60 to 0.

78.

150. The chemically strengthened glass-ceramics according to any one of claims 147 to 149, characterized in that: The spinel crystal is (Zn, Mg)Al2O4; And / or, the chemically strengthened glass-ceramics further comprises secondary crystalline tetragonal zirconia; And / or, the crystallinity of the chemically strengthened glass-ceramics is ≥20.00wt%; And / or, in the chemically strengthened glass-ceramics, the average grain size is ≤15.0 nm; And / or, the Young's modulus of the chemically strengthened glass-ceramics is ≥100 GPa.

151. The chemically strengthened glass-ceramics according to claim 150, characterized in that The chemically strengthened glass-ceramics has a crystallinity of 20.00 to 50.00 wt %.

152. The chemically strengthened glass-ceramics according to claim 150, characterized in that The chemically strengthened glass-ceramics has a crystallinity of 30.00 to 50.00 wt %.

153. The chemically strengthened glass-ceramics according to claim 150, characterized in that The chemically strengthened glass-ceramics has a crystallinity of 35.00 to 45.00 wt %.

154. The chemically strengthened glass-ceramics according to claim 150, characterized in that In the chemically strengthened glass-ceramics, an average crystal grain size is 1.0 to 15.0 nm.

155. The chemically strengthened glass-ceramics according to claim 150, characterized in that In the chemically strengthened glass-ceramics, an average crystal grain size is 1.0 to 10.0 nm.

156. The chemically strengthened glass-ceramics according to claim 150, characterized in that In the chemically strengthened glass-ceramics, an average grain size is 4.5 to 8.0 nm.

157. The chemically strengthened glass-ceramics according to claim 150, characterized in that The Young's modulus of the chemically strengthened glass-ceramics is ≥110 GPa.

158. The chemically strengthened glass-ceramics according to claim 150, characterized in that The Young's modulus of the chemically strengthened glass-ceramics is 114 GPa≤Young's modulus≤140 GPa.

159. Application of the strengthened glass-ceramics described in any one of claims 1-140, the strengthened glass-ceramics prepared by the preparation method described in any one of claims 141-146, or the chemically strengthened glass-ceramics described in any one of claims 147-158 in mobile phone displays, tablet computer displays, handheld game consoles, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

160. Use of the strengthened microcrystalline glass described in any one of claims 1-140, the strengthened microcrystalline glass prepared by the preparation method described in any one of claims 141-146, or the chemically strengthened microcrystalline glass described in any one of claims 147-158 in electronic terminals.

161. Use of the strengthened microcrystalline glass described in any one of claims 1-140, the strengthened microcrystalline glass prepared by the preparation method described in any one of claims 141-146, or the chemically strengthened microcrystalline glass described in any one of claims 147-158 in portable digital devices.

162. A display screen, characterized in that: The display screen includes the strengthened microcrystalline glass as described in any one of claims 1-140, or the strengthened microcrystalline glass prepared by the preparation method as described in any one of claims 141-146, or the chemically strengthened microcrystalline glass as described in any one of claims 147-158.

163. The display screen according to claim 162, characterized in that The display screens shown include a mobile phone display screen, a tablet computer display screen, a vehicle central control screen, or a smart home touch screen.

164. An electronic terminal, characterized in that: The electronic terminal shown includes the strengthened microcrystalline glass as described in any one of claims 1-140, or the strengthened microcrystalline glass prepared by the preparation method as described in any one of claims 141-146, or the chemically strengthened microcrystalline glass as described in any one of claims 147-158.

165. A windshield, characterized in that: The windshield glass shown includes the strengthened microcrystalline glass as described in any one of claims 1-140, or the strengthened microcrystalline glass prepared by the preparation method as described in any one of claims 141-146, or the chemically strengthened microcrystalline glass as described in any one of claims 147-158.

166. The windshield according to claim 165, characterized in that The windshield shown includes a vehicle windshield, an aircraft windshield or an aircraft windshield.

Citation Information

Patent Citations

  • Spinel transparent microcrystalline glass with low melting temperature, preparation method and performance enhancing method thereof

    CN111018354A

  • Spinel microcrystalline glass capable of being chemically strengthened as well as preparation method and application of spinel microcrystalline glass

    CN115010369A

Cited By

  • Chemically strengthened microcrystalline glass and preparation thereof

    CN121672942A

  • Chemically strengthened microcrystalline glass and preparation thereof

    CN121672942B

  • Precursor glass for preparing spinel glass ceramics

    CN121698567A

  • Spinel glass ceramic and preparation method thereof

    CN121698570A

  • Spinel microcrystalline glass and preparation method thereof

    CN121698570B